Positive electrode and all-solid-state secondary battery including same

By using composite positive electrode active substances in all-solid secondary batteries, the side reaction problem between the positive electrode active substances and the solid electrolyte is solved, and better cycle characteristics and performance stability are achieved.

CN119895590APending Publication Date: 2025-04-25SAMSUNG SDI CO LTD

Patent Information

Application Number
CN202380066714.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-29
Filing Date
2023-09-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In all-solid secondary batteries, side reactions between positive electrode active substances and solid electrolytes lead to deterioration of performance.

Method used

A new positive electrode containing a composite positive electrode active material is adopted, which consists of lithium transition metal oxide, first metal oxide and first carbon material. The shell layer is formed by a matrix of the first metal oxide and the first carbon material, and the side reaction between the lithium transition metal oxide and the solid electrolyte is suppressed.

Benefits of technology

It effectively suppresses side reactions, improves the circulation characteristics of all-solid-state secondary batteries, and improves the performance stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119895590A_ABST
    Figure CN119895590A_ABST
Patent Text Reader

Abstract

Provided are a positive electrode for an all-solid-state secondary battery and an all-solid-state secondary battery including the same, in which the positive electrode includes a positive electrode current collector and a positive electrode active material layer provided on the positive electrode current collector, in which the positive electrode active material layer includes a composite positive electrode active material and a sulfide-based solid electrolyte, a composite positive electrode active material includes a core including a lithium transition metal oxide and a shell disposed on a surface of the core, the shell including at least one first metal oxide and a first carbon-based material, the first metal oxide being disposed in a matrix of the first carbon-based material, the first metal oxide being represented by the formula MaOb (wherein 0 lt; a < = 3, 0lt; blt; and b is not an integer if a is 1, 2 or 3), where M is at least one metal selected from Group 2 to Group 16 of the periodic table, the lithium transition metal oxide includes nickel, and the nickel content is 80 mol% or more with respect to the total number of moles of the transition metal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] One or more embodiments relate to a positive electrode and an all-solid-state secondary battery including the positive electrode. Background Art

[0002] Recently, due to industrial demands, batteries with high energy density and safety have been actively developed. For example, lithium batteries are being commercialized not only in the fields of information-related devices and communication devices but also in the vehicle field. In the vehicle field, since vehicles are related to life, safety is particularly important.

[0003] Lithium batteries use a liquid electrolyte including a flammable organic solvent as an electrolyte. Therefore, if a short circuit occurs, there is a possibility of overheating and catching fire. All-solid-state batteries using a solid electrolyte instead of a liquid electrolyte have been proposed.

[0004] Since all-solid-state batteries do not use flammable organic solvents, even if a short circuit occurs, the possibility of fire or explosion can be significantly reduced. In such all-solid-state batteries, the safety can be significantly improved compared to lithium batteries using a liquid electrolyte. Summary of the Invention

[0005] Technical Problem

[0006] One or more embodiments include a novel positive electrode in which a side reaction between a positive electrode active material and a solid electrolyte is suppressed, thereby preventing deterioration of the performance of an all-solid-state secondary battery.

[0007] One or more embodiments include an all-solid-state secondary battery including the positive electrode.

[0008] Technical Solution

[0009] According to one or more embodiments, a positive electrode for an all-solid-state secondary battery includes: a positive electrode current collector; and a positive electrode active material layer disposed on the positive electrode current collector, wherein the positive electrode active material layer includes a composite positive electrode active material and a sulfide-based solid electrolyte, the composite positive electrode active material includes: a core including a lithium transition metal oxide; and a shell disposed on the surface of the core, wherein the shell includes at least one first metal oxide and a first carbonaceous material, and the first metal oxide is disposed in a matrix of the first carbonaceous material, the first metal oxide is represented by the formula M a O b (where 0 < a ≤ 3, 0 < b < 4, and if a is 1, 2, or 3, then b is not an integer, and M is at least one metal selected from Groups 2 to 16 of the periodic table), the lithium transition metal oxide includes nickel, and the nickel content is 80 mol% or more relative to the total molar amount of transition metals.

[0010] According to one or more embodiments, a positive electrode includes the above-described positive electrode active material.

[0011] According to one or more embodiments, an all-solid-state secondary battery includes:

[0012] The positive electrode; the negative electrode; and the solid electrolyte layer are arranged between the positive electrode and the negative electrode.

[0013] Beneficial Effects

[0014] According to one aspect, using a novel positive electrode, a side reaction between a lithium transition metal oxide and a solid electrolyte can be suppressed, thereby providing an all-solid-state secondary battery with improved cycle characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is a cross-sectional view of a positive electrode according to an embodiment.

[0016] Figure 2 is a schematic cross-sectional view of a composite positive electrode active material particle according to an embodiment.

[0017] Figure 3 is a cross-sectional view of a composite positive electrode active material particle in the art.

[0018] Figure 4 is a cross-sectional view of an all-solid-state secondary battery according to an embodiment.

[0019] Figure 5 is a cross-sectional view of an all-solid-state secondary battery according to an embodiment.

[0020] Figure 6 is a cross-sectional view of an all-solid-state secondary battery according to an embodiment.

[0021] Figure 7 is a cross-sectional view of an all-solid-state secondary battery according to an embodiment.

[0022] Figure 8 is a cross-sectional view of a dual-cell all-solid-state secondary battery according to an embodiment.

[0023] Figure 9a is a scanning electron microscope image of a cross section of the composite positive electrode active material prepared in Example 1.

[0024] Figure 9b : is an energy dispersive X-ray spectroscopy (EDS) mapping image of a cross section of the composite positive electrode active material prepared in Example 1.

[0025] Fig.10are X-ray photoelectron spectroscopy (XPS) images of the bare NCA94 prepared in Comparative Example 1, the composite prepared in Preparation Example 1, and the composite positive electrode active material prepared in Example 1.

[0026] Fig.11 1 and 2 are Raman spectral images of the composite prepared in Preparation Example 1 and the composite positive electrode active material prepared in Example 1.

[0027] <Description of Reference Numerals Representing Main Elements of the Drawings>

[0028] 1: All-solid-state secondary battery; 10: Positive electrode

[0029] 11: Positive electrode current collector; 12: Positive electrode active material layer

[0030] 20: negative electrode; 21: negative electrode current collector

[0031] 22: first negative electrode active material layer; 30: solid electrolyte layer

[0032] 100: core; 200: shell

[0033] 210: first metal oxide; 220: first carbon-based material

[0034] 300: composite positive electrode active material; 400: solid electrolyte. DETAILED DESCRIPTION

[0035] Now will refer to the embodiment in detail, the example of embodiment is shown in the accompanying drawings, wherein the same reference numerals always refer to the same element. In this regard, the embodiment presented can have different forms and should not be construed as being limited to the description set forth herein. Therefore, the embodiment is described below only by reference to the accompanying drawings to explain the aspects of this specification. As used herein, the term "and / or" includes any combination and all combinations of one or more of the related listed items. If a statement such as "at least one (kind / person) of ... " is after a column of elements, the entire column of elements is modified without modifying the individual elements in the column.

[0036] Various embodiments are shown in the accompanying drawings. However, the inventive concept may be embodied in different forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that the disclosure will be thorough and complete and fully convey the scope of the inventive concept to those skilled in the art. The same reference numerals represent the same elements.

[0037] If an element is described as being "on" another element, it will be understood that the element may be directly disposed on the other element or another element may be interposed between them. On the other hand, if an element is described as being "directly on" another element, another element may not be interposed between them.

[0038] It will be understood that although the terms "first", "second", and "third" may be used herein to describe various elements, components, regions, layers, and / or parts, these elements, components, regions, layers, and / or parts should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer, or part from another element, component, region, layer, or part. Therefore, without departing from the teachings of this specification, the first element, first component, first region, first layer, or first part described below may be referred to as a second element, second component, second region, second layer, or second part.

[0039] The terms used herein are intended only to describe specific embodiments and are not intended to limit the inventive concept. As used herein, unless the content clearly indicates otherwise, the singular forms "one", "one (kind / person)" and "the (described)" are intended to include plural forms including "at least one (kind / person)". "At least one (kind / person)" should not be interpreted as being limited to the singular. As used herein, the term "and / or" includes any combination and all combinations of one or more of the relevant listed items. If the terms "include", "comprising" and / or variations thereof are used in the detailed description, it is indicated that there are stated features, regions, integers (whole), steps, operations, elements and / or components, but the presence or addition of one or more other features, regions, integers (whole), steps, operations, elements, components and / or groups thereof are not excluded.

[0040] Spatially relative terms such as "under," "below," "lower," "above," and "upper" may be used herein to easily describe the relationship of one element or feature to another. It will be understood that the spatially relative terms are intended to encompass different orientations of the device in use or operation in addition to the orientation shown in the drawings. For example, if the device in the drawings is flipped, an element described as "under" or "beneath" other elements or features will subsequently be oriented "above" or "on" the other elements or features. Thus, the example term "under" may encompass both above and below orientations. The device may be otherwise oriented (rotated 90 degrees or in other orientations), and the spatially relative terms used herein may be interpreted accordingly.

[0041] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those commonly understood by those skilled in the art to which the disclosure belongs. In addition, it will be further understood that terms (such as those defined in commonly used dictionaries) should be interpreted as having a meaning consistent with their meaning in the context of the relevant art and disclosure, and will not be interpreted in an idealized or overly formal sense unless explicitly defined as such herein.

[0042] Embodiments are described herein with reference to cross-sectional views which are schematic diagrams of idealized embodiments. As such, variations in the illustrated shapes resulting from, for example, manufacturing techniques and / or tolerances are expected. Therefore, the embodiments described herein should not be construed as being limited to the specific shapes of the regions shown herein, but may include shape deviations, for example, resulting from manufacturing. For example, a region shown or described as flat may typically be rough and / or have nonlinear features. In addition, sharply drawn angles may be rounded. Therefore, the regions shown in the drawings are schematic in nature, and their shapes are not intended to illustrate the actual shapes of the regions, and are not intended to limit the scope of the claims.

[0043] "Group" refers to a Group of the Periodic Table of the Elements according to the International Union of Pure and Applied Chemistry ("IUPAC") Group 1 to Group 18 classification system.

[0044] The term "particle size" as used herein refers to the average diameter if the particles are spherical, and to the average major axis length if the particles are non-spherical. Particle size can be measured using a particle size analyzer (PSA). "Particle size" is, for example, the average particle size. "Average particle size" refers to, for example, D50 as the median particle size.

[0045] If the particle size distribution measured by the laser diffraction method is calculated from particles having a smaller particle size, D50 is the particle size corresponding to 50% cumulative volume.

[0046] If the particle size distribution measured by the laser diffraction method is calculated from particles having a smaller particle size, D90 is the particle size corresponding to 90% of the cumulative volume.

[0047] If the particle size distribution measured by the laser diffraction method is calculated from particles having a smaller particle size, D10 is the particle size corresponding to 10% cumulative volume.

[0048] The term "metal" as used herein includes all metals and metalloids (such as silicon and germanium in either the elemental or ionic state).

[0049] As used herein, the term "alloy" refers to a mixture of two or more metals.

[0050] As used herein, the term "electrode active material" refers to an electrode material that can undergo lithiation and delithiation.

[0051] As used herein, the term "positive electrode active material" refers to an electrode material that can undergo lithiation and delithiation.

[0052] As used herein, the term "negative electrode active material" refers to a negative electrode material that can undergo lithiation and delithiation.

[0053] As used herein, the term "lithiation" and variations thereof refer to the process of adding lithium to an electrode active material.

[0054] As used herein, the term "delithiation" and variations thereof refer to the process of removing lithium from an electrode active material.

[0055] As used herein, the term "charging" and variations thereof refers to the process of providing electrochemical energy to a battery.

[0056] As used herein, the term "discharge" and variations thereof refer to the process of removing electrochemical energy from a battery.

[0057] As used herein, the term "positive electrode" and variations thereof refers to the electrode that undergoes electrochemical reduction and lithiation during the discharge process.

[0058] As used herein, the term "negative electrode" and variations thereof refer to the electrode that undergoes electrochemical oxidation and delithiation during the discharge process.

[0059] Although specific embodiments have been described, alternatives, modifications, variations, improvements, and substantial equivalents that are not currently foreseeable or may not be foreseeable may occur to the applicant or other persons skilled in the art. Therefore, the appended claims as filed and as they may be amended are intended to include all such alternatives, modifications, variations, improvements, and substantial equivalents.

[0060] Hereinafter, a positive electrode for an all-solid-state secondary battery and an all-solid-state secondary battery including the positive electrode according to an embodiment will be described in more detail.

[0061] [Positive electrode]

[0062] The positive electrode for an all-solid-state secondary battery according to an embodiment may include a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, wherein the positive electrode active material layer includes a composite positive electrode active material and a sulfide-based solid electrolyte, the composite positive electrode active material includes a core including a lithium transition metal oxide and a shell disposed on a surface of the core, the shell includes at least one first metal oxide and a first carbon-based material, and the first metal oxide is disposed in a matrix of the first carbon-based material, wherein the first metal oxide is represented by the formula M a Ob (wherein, 0 < a ≤ 3, 0 < b < 4, and if a is 1, 2, or 3, then b is not an integer, and M is at least one metal selected from Groups 2 to 16 of the periodic table) indicates that the lithium transition metal oxide includes nickel, and the nickel content is 80 mol% or more relative to the total moles of the transition metal.

[0063] The composite positive electrode active material may include a core and a shell. Since the shell includes a first metal oxide disposed in a matrix of a first carbonaceous material, electron conductivity due to the matrix of the first carbonaceous material and ion conductivity due to the first metal oxide can be provided simultaneously. The matrix of the first carbonaceous material and the first metal oxide may form, for example, a first composite. The first composite may be used as a mixed conductor having electron conductivity and ion conductivity. Since the first composite provides electron conductivity and ion conductivity simultaneously, a stable interface can be formed between the core of the composite positive electrode active material and the solid electrolyte. During charging / discharging of the all-solid-state secondary battery, an increase in the interfacial resistance between the core of the composite positive electrode active material and the solid electrolyte can be effectively suppressed. As a result, the cycle characteristics of the all-solid-state secondary battery including the positive electrode can be improved.

[0064] In the composite positive electrode active material having a shell made of a carbonaceous material, the carbonaceous material can be used as a carbon electrode that transfers only electrons, thereby promoting the decomposition of the solid electrolyte at a high potential. Therefore, the composite positive electrode active material having a shell made of a carbonaceous material is not suitable for application to a positive electrode including a solid electrolyte. In contrast, in the positive electrode active material having a shell including a first composite, since the first composite is used as a mixed conductor that transfers electrons and ions, decomposition of the solid electrolyte can be suppressed even at a high potential. Therefore, the composite positive electrode active material including a shell containing a first composite is suitable for application to a positive electrode including a solid electrolyte.

[0065] Referring to Figure 1 and Figure 2 , the positive electrode 10 includes a positive electrode current collector 11 and a positive electrode active material layer 12 disposed on the positive electrode current collector 11. The positive electrode active material layer 12 may include a composite positive electrode active material 300 and a sulfide-based solid electrolyte 400. The composite positive electrode active material 300 may include a core 100 containing a lithium transition metal oxide and a shell 200 disposed on the surface of the core 100. The shell 200 may include at least one first metal oxide 210 and a first carbonaceous material 220, and the first metal oxide 210 may be disposed in a matrix of the first carbonaceous material 220. The first metal oxide 210 may be represented by the formula M a O b(where 0 < a ≤ 3, 0 < b < 4, and if a is 1, 2, or 3, then b is not an integer, and M is at least one metal selected from Groups 2 to 16 of the periodic table). The lithium transition metal oxide may include nickel, and the nickel content may be 80 mol% or more relative to the total number of moles of the transition metal. The positive electrode 10 may be used in an all-solid-state secondary battery.

[0066] [Positive electrode: Composite positive electrode active material]

[0067] Referring to Figure 2 , the composite positive electrode active material 300 includes a core 100 and a shell 200 disposed continuously or discontinuously along the surface of the core 100. The shell 200 may cover the whole or a part of the core 100. The core 100 may include a lithium transition metal oxide, and the shell 200 may include a first metal oxide 210 and a first carbonaceous material 220. The shell 200 may include, for example, a first composite including a plurality of first metal oxides 210 disposed in a matrix of the first carbonaceous material 220.

[0068] The first metal oxide may include a first metal, and the first metal may include, for example, at least one selected from Al, Nb, Mg, Sc, Ti, Zr, V, W, Mn, Fe, Co, Pd, Cu, Ag, Zn, Sb, Si, and Se. The first metal oxide 210 may include, for example, those selected from Al2O z (where 0 < z < 3), NbO x (where 0 < x < 2.5), MgO x (where 0 < x < 1), Sc2O z (where 0 < z < 3), TiO y (where 0 < y < 2), ZrO y (where 0 < y < 2), V2O z (where 0 < z < 3), WO y (where 0 < y < 2), MnO y (where 0 < y < 2), Fe2O z (where 0 < z < 3), Co3O w (where 0 < w < 4), PdO x (where 0 < x < 1), CuO x (where 0 < x < 1), AgO x (where 0 < x < 1), ZnO x (where 0 < x < 1), Sb2O z (where 0 < z < 3), SiO z (where 0 < z < 2) and SeO y(wherein, 0 < y < 2). Since the shell 200 includes the first composite, and the first composite includes the matrix of the first carbonaceous material 220 and the first metal oxide 210, the shell 200 can be used as a buffer layer having ionic conductivity and electronic conductivity. Since the first metal oxide 210 is disposed in the matrix of the first carbonaceous material 220, the voltage resistance stability of the composite positive electrode active material 300 can be further improved. For example, the shell 200 may include Al2O as the first metal oxide 210 x (where 0 < x < 3). The shell 200 may include, for example, a first composite in which a plurality of first metal oxides 210 are disposed in the matrix of the first carbonaceous material 220. Since the first composite serves as a mixed conductor providing both ionic conductivity and electronic conductivity, side reactions between the lithium transition metal oxide core and the sulfide-based solid electrolyte can be suppressed. As a result, the cycle characteristics of the all-solid-state secondary battery including the composite positive electrode active material can be improved. In contrast, referring to Figure 3 , the composite positive electrode active material 300 in the art may include a core 100 and a shell 200, and the shell 200 may be composed of a carbonaceous material. In such a composite positive electrode active material 300 in the art, since the shell 200 is made of a carbonaceous material having low ionic conductivity, decomposition of the solid electrolyte at a high potential may be promoted, thereby causing deterioration of the all-solid-state secondary battery. Alternatively, referring to Figure 3 , the composite positive electrode active material 300 in the art may include a core 100 and a shell 200, and the shell 200 may be made of a metal oxide material. In such a composite positive electrode active material 300 in the art, since the shell 200 is composed of a metal oxide material having low electronic conductivity, the internal resistance of the positive electrode may be increased, thereby deteriorating the cycle characteristics of the all-solid-state secondary battery.

[0069] The first carbonaceous material may be, for example, a crystalline carbonaceous material. The first carbonaceous material may include, for example, a carbonaceous nanostructure. The first carbonaceous material may include, for example, a carbonaceous two-dimensional nanostructure. The first carbonaceous material may include, for example, graphene. In this case, since the shell including graphene and / or its matrix is flexible, the shell can easily adapt to the volume change of the composite positive electrode active material during charge / discharge, thereby suppressing the occurrence of cracks inside the composite positive electrode active material. Since graphene has high electronic conductivity, the interfacial resistance between the composite positive electrode active material and the solid electrolyte can be reduced. Existing nanostructured carbonaceous materials that do not include the first metal oxide may be prone to aggregation, and thus may be difficult to coat along the surface of the lithium transition metal oxide core.

[0070] The shell may include, for example, a first metal oxide and a first carbon-based material. Since the first carbon-based material is derived from, for example, a graphene matrix, the first carbon-based material may have a relatively low density and a high porosity compared to existing carbon-based materials derived from graphite-based materials. The d002 interplanar spacing of the first carbon-based material may be, for example, or larger, or larger, or larger, or larger, or larger, or larger, or The d002 interplanar spacing of the first carbon-based material included in the shell may be, for example, about to about about to about about to about about to about or about to about In contrast, the d002 interplanar spacing of existing carbon-based materials derived from graphite-based materials can be, for example, or smaller or to Since the first metal oxide has voltage resistance and / or ion conductivity and the first carbon-based material has electronic conductivity, during charge / discharge at high voltage, it is possible to prevent the degradation of the lithium transition metal oxide included in the core and prevent side reactions between the core and the solid electrolyte. The shell may include, for example, at least one first metal oxide or two or more different first metal oxides. As a result, the high temperature cycle characteristics of a lithium battery including the above-mentioned composite positive electrode active material can be improved.

[0071] The shell may further include at least one second metal oxide different from the first metal oxide. The second metal oxide may be represented by the formula a O c(where 0 < a ≤ 3, 0 < c ≤ 4, and if a is 1, 2, or 3, then c is an integer, and M is at least one metal selected from Groups 2 to 16 of the Periodic Table). For example, the second metal oxide may include the same metal as the first metal oxide, and c / a, which is the ratio of c to a for the second metal oxide, may have a value greater than b / a, which is the ratio of b to a for the first metal oxide. For example, c / a > b / a. The second metal oxide may be disposed, for example, in a matrix of the first carbonaceous material. Since the second metal oxide is additionally disposed in the matrix of the first carbonaceous material, the uniformity of the shell disposed on the core can be further improved, and the voltage resistance stability of the composite positive electrode active material can be further improved. For example, the shell may include Al2O3 as the second metal oxide. The second metal oxide may be selected from, for example, Al2O3, NbO, NbO2, Nb2O5, MgO, Sc2O3, TiO2, ZrO2, V2O3, WO2, MnO2, Fe2O3, Co3O4, PdO, CuO, AgO, ZnO, Sb2O3, SiO2, and SeO2. The first metal oxide may be, for example, a reduction product of the second metal oxide. A part or all of the second metal oxide may be reduced to obtain the first metal oxide. Therefore, the first metal oxide has an oxygen content and a metal oxidation number lower than those of the second metal oxide. The shell may include, for example, Al2O x (where 0 < x < 3) and Al2O3 as the second metal oxide.

[0072] The shell may include, for example, the first carbonaceous material, and the core may include, for example, a lithium transition metal oxide. Additionally, the first carbonaceous material may be chemically bonded, for example, by a chemical bond to the transition metal of the lithium transition metal oxide. The carbon atoms (C) of the first carbonaceous material may be chemically bonded, for example, using oxygen atoms through a C-O-Me bond (e.g., a C-O-Ni bond or a C-O-Co bond) to the transition metal (Me) of the lithium transition metal oxide. The first carbonaceous material disposed in the shell may be chemically bonded by a chemical bond to the lithium transition metal oxide disposed in the core, thereby allowing the core and the shell to form a composite. Therefore, the composite positive electrode active material can be distinguished from a simple physical mixture of the first carbonaceous material and the lithium transition metal oxide. Additionally, the first metal oxide may also be chemically bonded by a chemical bond to the first carbonaceous material. Here, the chemical bond may be, for example, a covalent bond or an ionic bond.

[0073] The shell may include, for example, at least one selected from the first metal oxide and the second metal oxide, and the particle size of at least one selected from the first metal oxide and the second metal oxide may be, for example, in the range of about 1 nm to about 100 nm, about 1 nm to about 50 nm, about 1 nm to about 30 nm, about 5 nm to about 30 nm, or about 10 nm to about 30 nm. Since the first metal oxide and / or the second metal oxide have a particle size in this nanometer range, the first metal oxide and / or the second metal oxide may be more evenly distributed in the matrix of the first carbon-based material. If the particle size of at least one selected from the first metal oxide and the second metal oxide is excessively increased, the internal resistance of the composite positive electrode active material may increase due to the increase in the thickness of the shell. If the particle size of at least one selected from the first metal oxide and the second metal oxide is excessively reduced, it may be difficult to disperse evenly.

[0074] The shell may include, for example, a first metal oxide and / or a second metal oxide, and may include a first carbon-based material. The first carbon-based material may be arranged in a direction in which the first carbon-based material protrudes from the surface of the first metal oxide and / or the second metal oxide. The first carbon-based material may be epitaxially grown on the surface of the first metal oxide and / or the second metal oxide to be arranged in a direction in which the first carbon-based material protrudes from the surface of the first metal oxide and / or the second metal oxide. The first carbon-based material arranged in a direction in which the first carbon-based material protrudes from the surface of the first metal oxide and / or the second metal oxide may include, for example, a carbon-based two-dimensional nanostructure, a carbon-based flake or graphene.

[0075] The shell may further include, for example, a second carbon-based material, a third metal oxide, or a combination thereof.

[0076] The shell may also include, for example, a second carbon-based material. The second carbon-based material may include, for example, fibrous carbon having an aspect ratio of 10 or more. Therefore, since the shell includes the second carbon-based material, the conductive path of the composite positive electrode active material may be further extended. The second carbon-based material may form a three-dimensional conductive network between a plurality of composite positive electrode active materials to reduce the internal resistance of the positive electrode including the composite positive electrode active material. The fibrous carbon may be fixed to the composite positive electrode active material, thereby forming a uniform and stable three-dimensional conductive network between a plurality of composite positive electrode active materials. Therefore, since the composite positive electrode active material includes the second carbon-based material, the high rate characteristics of the all-solid-state secondary battery including the composite positive electrode active material may be improved. The second carbon-based material may protrude from the surface of the composite positive electrode active material. Therefore, the second carbon-based material may effectively provide a conductive network between a plurality of composite positive electrode active material particles. The second carbon-based material may be disposed in a matrix of the first carbon-based material, and thus may be easily coated on the core. The matrix of the first carbon-based material may be used as a binder for bonding the core to the second carbon-based material. If there is no matrix of the first carbon-based material, it is difficult for the second carbon-based material to be easily attached to the core, or the second carbon-based material may be easily detached from the core during the preparation of the slurry for the positive electrode. If a binder is added to bond the lithium transition metal oxide (core) and the second carbon-based material, the core may be covered with an insulating binder, which may increase the internal resistance of the composite positive electrode active material. If the core covered with the second carbon-based material and the binder is subjected to high temperature heat treatment to carbonize the binder, the core and the second carbon-based material may deteriorate during the heat treatment process. The second carbon-based material may have an aspect ratio of 10 or more or 20 or more. The second carbon-based material may have an aspect ratio of, for example, about 10 to about 10,000, about 10 to about 5,000, about 10 to about 1,000, about 10 to about 500, about 10 to about 100, or about 10 to about 50. The aspect ratio of the second carbon-based material can be, for example, the ratio of the length of the major axis passing through the center of the second carbon-based material to the length of the minor axis passing through the center of the second carbon-based material and perpendicular to the major axis (i.e., the diameter of the second carbon-based material). The diameter of the second carbon-based material can be, for example, 50nm or less, 30nm or less, 20nm or less, or 10nm or less. The second carbon-based material can have, for example, a diameter of about 1nm to about 50nm, about 1nm to about 30nm, or about 1nm to about 10nm. If the diameter of the second carbon-based material is too large, the absolute number of strands per volume may be reduced, and therefore the effect of reducing internal resistance may not be significant. If the diameter of the second carbon-based material is too small, it may be difficult to disperse evenly.The second carbon-based material can have, for example, a length of about 100nm to 1,000μm, about 100nm to about 500μm, about 100nm to about 100μm, about 100nm to about 50μm, about 100nm to about 10μm, about 100nm to about 5μm, about 100nm to about 2μm, about 100nm to about 1μm, about 100nm to about 500nm, or about 100nm to about 300nm. As the length of the second carbon-based material increases, the internal resistance of the electrode can be reduced. If the length of the second carbon-based material is too short, it may be difficult to provide an effective conductive path. The second carbon-based material may include, for example, carbon nanofibers, carbon nanotubes, or a combination thereof. Carbon nanotubes may include, for example, carbon nanotube primary structures, carbon nanotube secondary structures formed by aggregating multiple carbon nanotube primary particles, or a combination thereof. The carbon nanotube primary structure may be a carbon nanotube unit. The carbon nanotube primary structure may include, for example, single-walled carbon nanotubes (SWCNT), double-walled carbon nanotubes (DWCNT), multi-walled carbon nanotubes (MWCNT), or a combination thereof. The carbon nanotube secondary structure may be a structure formed by aggregating the carbon nanotube primary structure to completely or partially form a bundle type or a rope type. The carbon nanotube secondary structure may include, for example, a bundle type carbon nanotube, a rope type carbon nanotube, or a combination thereof.

[0077] The shell may further include, for example, a third metal oxide. The third metal oxide may include, for example, a lithium metal oxide. The lithium metal oxide may include, for example, lithium aluminum oxide (LAO), lithium titanium oxide (LTO), lithium zirconium oxide (LZO), lithium zirconium phosphate (LZP), or a combination thereof. Since the shell also includes a third metal oxide, the ionic conductivity of the composite positive electrode active material may be further improved. LAO may be, for example, LiAlO2. LTO may be, for example, Li4Ti5O 12 , Li2TiO3, etc. LZO may be, for example, Li2O-ZrO2. LZP may be, for example, Li2ZrP2O8.

[0078] The shell may have a thickness of, for example, about 10 nm to about 2 μm, about 30 nm to about 1 μm, about 50 nm to about 1 μm, about 100 nm to about 500 nm, about 100 nm to about 300 nm, or about 100 nm to about 200 nm. Since the shell has a thickness within such a range, the electronic conductivity of the positive electrode including the composite positive electrode active material can be further improved.

[0079] The shell may have, for example, a single-layer structure or a multi-layer structure. The multi-layer structure may have, for example, a two-layer to five-layer structure. The single-layer structure may have, for example, a first-layer structure including a first metal oxide or a first-layer structure including a first metal oxide and a second metal oxide. The multi-layer structure may include, for example, a first layer including a first metal oxide and a second layer including a second metal oxide. The multi-layer structure may include, for example, a first layer including a third metal oxide and a second layer including a first metal oxide and a second metal oxide. The multi-layer structure may include, for example, a first layer including a third metal oxide and a second layer including a first metal oxide and a second metal oxide. The multi-layer structure may include, for example, a first layer including a first metal oxide and a second layer including a third metal oxide. The multi-layer structure may include, for example, a first layer including a first metal oxide and a second layer including a third metal oxide. The multi-layer structure may include, for example, a first layer including a first metal oxide and a second layer including a third metal oxide.

[0080] The shell may be a dry coating prepared by a dry process. The dry process may include, for example, mechanical grinding, but one or more embodiments are not necessarily limited thereto. Any method used as a dry process in the art may be used.

[0081] Relative to the total weight of the composite positive electrode active material, the content of the shell can be about 5wt% or less, for example, it can be in the range of about 0.01wt% to about 5wt%, about 0.05wt% to about 4wt%, about 0.05wt% to about 3wt%, about 0.05wt% to about 2wt%, about 0.05wt% to about 1.05wt%, or about 0.05wt% to about 1wt%. The content of the first metal oxide can be, for example, in the range of about 0.006wt% to about 3wt%, about 0.03wt% to about 2.4wt%, about 0.03wt% to about 1.8wt%, about 0.03wt% to about 1.2wt%, or 0.03wt% to about 0.9wt%, or about 0.03wt% to about 0.6wt% of the total weight of the composite positive electrode active material. Since the composite positive electrode active material includes each of the shell and the first metal oxide within such a content range, the cycle characteristics of the lithium battery can be further improved.

[0082] The shell arranged along the surface of the core can be formed by coating the core with a second composite, for example, including a first metal oxide and a first carbonaceous material (such as graphene), via grinding or the like. Therefore, the shell arranged continuously or discontinuously along the surface of the core can include at least one of the second composite and / or the grinding product of the second composite, and the second composite includes the first metal oxide and the first carbonaceous material (such as graphene). The first metal oxide can be arranged in a matrix (for example, a graphene matrix) of the first carbonaceous material. The shell can be prepared, for example, by a second composite including the first metal oxide and the first carbonaceous material (such as graphene). In addition to the first metal oxide, the second composite can also include a second metal oxide. The second composite can include, for example, at least one first metal oxide. The second composite can include, for example, at least one first metal oxide and at least one second metal oxide.

[0083] The content of at least one selected from the second composite and its grinding product can be, for example, 5wt% or less, 3wt% or less, 2wt% or less, 1.5wt% or less, or 1wt% or less of the total weight of the composite positive electrode active material. The content of at least one selected from the second composite and its grinding product can be in the range of about 0.01wt% to about 5wt%, about 0.01wt% to about 4wt%, about 0.01wt% to about 3wt%, about 0.01wt% to about 2wt%, about 0.01wt% to about 1.5wt%, or about 0.01wt% to about 1wt%. Since the composite positive electrode active material includes at least one selected from the second composite and its grinding product within such a range, the cycle characteristics of the all-solid-state secondary battery including the composite positive electrode active material can be further improved.

[0084] The second composite may include at least one selected from the first metal oxide and the second metal oxide. At least one selected from the first metal oxide and the second metal oxide may have a particle size of about 1 nm to about 100 nm, about 1 nm to about 50 nm, about 1 nm to about 30 nm, about 5 nm to about 30 nm, or about 10 nm to about 30 nm. Since the first metal oxide and / or the second metal oxide have a particle size in this nanometer range, the first metal oxide and / or the second metal oxide can be more evenly distributed in the matrix of the first carbonaceous material of the second composite. Therefore, this second composite can be evenly coated on the core without agglomeration to form a shell. In addition, the first metal oxide and / or the second metal oxide may have a particle size in such a range, so it can be more evenly arranged on the core. Therefore, the first metal oxide and / or the second metal oxide can be evenly arranged on the core, so as to more effectively show the withstand voltage characteristics and ion conductivity. The particle size of the first metal oxide and / or the second metal oxide can be measured, for example, by a measuring device using a laser diffraction method or a dynamic light scattering method. The particle size can be measured using a laser scattering particle size distribution instrument (e.g., LA-920 manufactured by Horiba Corporation), and if the metal oxide particles are accumulated from small particles to 50% in volume conversion, the particle size is the value of the median diameter (D50). The uniformity deviation of at least one selected from the first metal oxide and / or the second metal oxide can be 3% or less, 2% or less, or 1% or less. The uniformity can be obtained, for example, by X-ray photoelectron spectroscopy (XPS). Therefore, at least one selected from the first metal oxide and the second metal oxide can have a uniformity deviation of 3% or less, 2% or less, or 1% or less and can be uniformly distributed in the composite.

[0085] The second composite may include a first carbon-based material. The first carbon-based material may have, for example, a branched structure, and at least one metal oxide selected from the first metal oxide and the second metal oxide may be distributed in the branched structure of the first carbon-based material. The branched structure of the first carbon-based material may include, for example, a plurality of first carbon-based material particles in contact with each other. Since the first carbon-based material has a branched structure, various conductive paths may be provided. The first carbon-based material may include, for example, graphene. Graphene may have, for example, a branched structure, and at least one metal oxide selected from the first metal oxide and the second metal oxide may be distributed in the branched structure of graphene. The branched structure of graphene may include, for example, a plurality of graphene particles in contact with each other. Since graphene has a branched structure, various conductive paths may be provided.

[0086] The first carbon-based material may have, for example, a spherical structure, and at least one metal oxide selected from the first metal oxide and the second metal oxide may be distributed in the spherical structure. The spherical structure of the first carbon-based material may have a size of about 50nm to about 300nm. The first carbon-based material with a spherical structure may be provided as a plurality of first carbon-based materials. Since the first carbon-based material has a spherical structure, the second composite may have a rigid structure. The first carbon-based material may include, for example, graphene. Graphene may have, for example, a spherical structure, and at least one metal oxide selected from the first metal oxide and the second metal oxide may be distributed in the spherical structure. The spherical structure of graphene may have a size of about 50nm to about 300nm. Graphene with a spherical structure may be provided as a plurality of graphenes. Since graphene has a spherical structure, the second composite may have a rigid structure.

[0087] The first carbon-based material may have, for example, a spiral structure in which a plurality of spherical structures are connected, and at least one metal oxide selected from the first metal oxide and the second metal oxide may be distributed in the spherical structure of the spiral structure. The spiral structure of the first carbon-based material may have a size of about 500nm to about 100μm. Since the first carbon-based material has a spiral structure, the second composite may have a rigid structure. The first carbon-based material may be, for example, graphene. Graphene may have, for example, a spiral structure in which a plurality of spherical structures are connected, and at least one metal oxide selected from the first metal oxide and the second metal oxide may be distributed in the spherical structure of the spiral structure. The spiral structure of graphene may have a size of about 500nm to about 100μm. Since graphene has a spiral structure, the second composite may have a rigid structure.

[0088] The first carbon-based material may have, for example, a cluster structure in which a plurality of spherical structures are aggregated, and at least one metal oxide selected from the first metal oxide and the second metal oxide may be distributed in the spherical structure of the cluster structure. The cluster structure of the first carbon-based material may have a size of about 0.5 mm to about 10 cm. Since the first carbon-based material has a cluster structure, the second composite may have a rigid structure. The first carbon-based material may include, for example, graphene. Graphene may have, for example, a cluster structure in which a plurality of spherical structures are aggregated, and at least one metal oxide selected from the first metal oxide and the second metal oxide may be distributed in the spherical structure of the cluster structure. The cluster structure of graphene may have a size of about 0.5 mm to about 10 cm. Since graphene has a cluster structure, the second composite may have a rigid structure.

[0089] The second composite may include, for example, a wrinkled polyhedral sphere structure, and at least one selected from the first metal oxide and the second metal oxide may be distributed inside or on the surface of the wrinkled polyhedral sphere structure. Due to the polyhedral sphere structure of the second composite, the second composite can be easily coated on the irregular surface unevenness of the core.

[0090] The second composite may have, for example, a planar structure, and at least one selected from the first metal oxide and the second metal oxide may be distributed inside or on the surface of the planar structure. Due to the two-dimensional planar structure of the second composite, the second composite can be easily coated on the irregular surface unevenness of the core.

[0091] The first carbonaceous material may extend a distance of 10 nm or less from the first metal oxide and may include at least 1 to 20 carbonaceous material layers. For example, the first carbonaceous material with a total thickness of 12 nm or less may be disposed on the first metal oxide by stacking a plurality of first carbonaceous material layers. For example, the first carbonaceous material may have a total thickness of about 0.6 nm to about 12 nm. The first carbonaceous material may include, for example, graphene. Graphene may extend a distance of 10 nm or less from the first metal oxide and may include at least 1 to 20 graphene layers. For example, a plurality of graphene layers may be stacked to arrange graphene with a total thickness of 12 nm or less on the first metal oxide. For example, graphene may have a total thickness of about 0.6 nm to about 12 nm.

[0092] The composite positive electrode active material may include a core, and the core may include, for example, a lithium transition metal oxide represented by a formula selected from the following Formula 1 to Formula 5.

[0093] Formula 1

[0094] Li a Ni x Co y M z O 2-b A b

[0095] In Formula 1, 1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0.8 ≤ x < 1, 0 ≤ y ≤ 0.3, 0 < z ≤ 0.3, x + y + z = 1, M may be manganese (Mn), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B) or a combination thereof, and

[0096] A may be F, S, Cl, Br or a combination thereof.

[0097] Formula 2

[0098] LiNi x Co y Mn z O2

[0099] Formula 3

[0100] LiNi x Co y Al z O2

[0101] In Formulas 2 and 3, 0.8 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.2, 0 < z ≤ 0.2, and x + y + z = 1.

[0102] Formula 4

[0103] LiNi x Co y Mn z Al w O2

[0104] In Formula 4, 0.8 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.2, 0 < z ≤ 0.2, 0 < w ≤ 0.2, and x + y + z + w = 1.

[0105] Formula 5

[0106] Li a Ni x Mn y M' z O 2-b A b

[0107] In Formula 5, 1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0.8 ≤ x < 1, 0 < y ≤ 0.2, 0 ≤ z ≤ 0.2, x + y + z = 1, M' can be niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B), or a combination thereof, and A can be F, S, Cl, Br, or a combination thereof.

[0108] The composite positive electrode active material may include, for example, a first composite positive electrode active material and a second composite positive electrode active material, and the first composite positive electrode active material and the second composite positive electrode active material may have different particle sizes. The first composite positive electrode active material may be a large-diameter composite positive electrode active material having a particle size larger than that of the second composite positive electrode active material. The second composite positive electrode active material may be a small-diameter composite positive electrode active material having a particle size smaller than that of the first composite positive electrode active material. For example, a second composite positive electrode active material having a particle size smaller than that of the first composite positive electrode active material may be disposed in the pores between the first composite positive electrode active material. The second composite positive electrode active material particles as small-diameter particles may be disposed in the pores between the first composite positive electrode active material particles as large-diameter particles, thereby improving the ionic conductivity and / or electronic conductivity of the positive electrode including the composite positive electrode active material. In addition, the energy density of the positive electrode including the composite positive electrode active material may be improved. As a result, the energy density of the all-solid-state secondary battery including the composite positive electrode active material can be improved and the cycle characteristics of the all-solid-state secondary battery including the composite positive electrode active material can be improved.

[0109] The first composite positive electrode active material may include, for example, secondary particles in which a plurality of primary particles are aggregated or may include primary particles having a particle size of 1 μm or more. The second composite positive electrode active material may include, for example, secondary particles in which a plurality of primary particles are aggregated or primary particles having a particle size of 1 μm or more. The first composite positive electrode active material and the second composite positive electrode active material may independently include, for example, secondary particles in which a plurality of primary particles are aggregated. The first composite positive electrode active material and the second composite positive electrode active material may independently include, for example, a core of a secondary particle in which a plurality of primary particles are aggregated and a shell disposed on the surface of the core. The primary particles constituting the secondary particles may have, for example, a size of less than 1 μm. The primary particles constituting the secondary particles may have, for example, a size of about 10 nm to about 700 nm, about 50 nm to about 500 nm, or about 100 nm to about 300 nm. The first composite positive electrode active material and the second composite positive electrode active material may independently include, for example, a core of a primary particle in which a particle size of 1 μm or more is included and a shell disposed on the surface of the core. The primary particle having a particle size of 1 μm or more may, for example, be a single particle (one-body particle). The single particle may have a particle size of, for example, about 1 μm to about 7 μm, about 1 μm to about 5 μm, or about 1 μm to about 3 μm.

[0110] For example, the first composite positive electrode active material and the second composite positive electrode active material may have a bimodal particle size distribution in the particle size distribution. For example, the composite positive electrode active material may have a bimodal particle size distribution having two peaks in the particle size distribution obtained using a particle size analyzer (PSA), etc. The bimodal particle size distribution may have a first peak corresponding to the first composite positive electrode active material and a second peak corresponding to the second composite positive electrode active material.

[0111] The particle size ratio of the first composite positive electrode active material to the second composite positive electrode active material may be, for example, in the range of about 3: 1 to about 40: 1, about 3: 1 to about 30: 1, about 3: 1 to about 20: 1, about 3: 1 to about 10: 1, or about 3: 1 to about 5: 1. Since the first composite positive electrode active material and the second composite positive electrode active material have a particle size ratio in such a range, the energy density and cycle characteristics of the lithium battery including the composite positive electrode active material can be further improved.

[0112] The first composite positive electrode active material may have a particle size of, for example, greater than about 8 μm and less than or equal to about 30 μm, about 9 μm to about 25 μm, about 9 μm to about 20 μm, about 9 μm to about 15 μm, or about 9 μm to about 12 μm. The particle size of the first composite positive electrode active material may be, for example, a median particle size (D50). The second composite positive electrode active material may have a particle size of, for example, greater than or equal to about 1 μm and less than about 8 μm, about 1 μm to about 7 μm, about 1 μm to about 6 μm, about 1 μm to about 5 μm, or about 1 μm to about 4 μm. The particle size of the second composite positive electrode active material may be, for example, a median particle size (D50). Since the first composite positive electrode active material and the second composite positive electrode active material have an average particle size within such a range, the energy density and / or cycle characteristics of the lithium battery including the composite positive electrode active material can be further improved. The particle size of the first composite positive electrode active material and the second composite positive electrode active material may be measured, for example, by a measuring device using a laser diffraction method or a dynamic light scattering method. The particle size can be measured using a laser scattering particle size distribution analyzer (eg, LA-920 manufactured by Horiba Corporation), and may be a value of a median diameter (D50) if metal oxide particles accumulate to 50% from small particles in volume distribution.

[0113] The weight ratio of the first composite positive electrode active material to the second composite positive electrode active material may be, for example, in the range of about 90:10 to about 60:40, about 85:15 to about 65:35, about 80:20 to about 65:35, or about 75:25 to about 65:35. Since the first composite positive electrode active material and the second composite positive electrode active material have a weight ratio in such a range, the energy density and / or cycle characteristics of a lithium battery including the composite positive electrode active material may be further improved.

[0114] [Positive electrode: solid electrolyte]

[0115] The positive electrode active material layer may include a sulfide solid electrolyte. The sulfide solid electrolyte may include, for example, a crystalline sulfide solid electrolyte, an amorphous sulfide solid electrolyte, a glassy sulfide solid electrolyte, a glass ceramic sulfide solid electrolyte, or a combination thereof. The structure of the sulfide solid electrolyte may be selected according to the desired performance of the all-solid-state secondary battery. The sulfide solid electrolyte may be, for example, crystalline or amorphous.

[0116] Sulfide-based solid electrolytes may include, for example, Li2S-P2S5, Li2S-P2S5-LiX (wherein X is a halogen element), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (wherein m and n are each positive numbers, and Z is one selected from Ge, Zn and Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (wherein p and q are each positive numbers, and M is one selected from P, Si, Ge, B, Al, Ga and In), Li 7-x PS 6-x Cl x (where 0≤x≤2), Li 7-x PS 6-x Br x (where 0≤x≤2) and Li 7-x PS 6-x I x(wherein, 0≤x≤2). A sulfide solid electrolyte can be prepared by treating a starting material such as Li2S or P2S5 by melt quenching or mechanical grinding. In addition, after such treatment, heat treatment may be performed. The solid electrolyte may be in an amorphous state, a crystalline state, or a mixture state of amorphous and crystalline. In addition, the solid electrolyte may be a material that includes at least sulfur (S), phosphorus (P), and lithium (Li) as constituent elements, such as the material of the above-mentioned sulfide solid electrolyte. For example, the solid electrolyte may be a material including Li2S-P2S5. If a material including Li2S-P2S5 is used as a sulfide solid electrolyte material for forming a solid electrolyte, the mixed molar ratio of Li2S to P2S5 (e.g., Li2S:P2S5) may be in the range of about 50:50 to about 90:10.

[0117] The sulfide-based solid electrolyte may include, for example, an argyrodite-type solid electrolyte represented by Formula 6 below.

[0118] Formula 6

[0119] Li + 12-n-x A n+ X 2- 6-x Y - x

[0120] In Formula 1, A may be P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb or Ta, X may be S, Se or Te, Y may be Cl, Br, I, F, CN, OCN, SCN or N3, 1≤n≤5 and 1≤x≤2. The sulfide-based solid electrolyte may be, for example, a sulfide-based solid electrolyte selected from Li 7-x PS 6-x Cl x (where 0≤x≤2), Li 7-x PS 6-x Br x (where 0≤x≤2) and Li 7-x PS 6-x I x (wherein 0≤x≤2) is an argyrodite-type compound (i.e., an argyrodite-type solid electrolyte). The sulfide-based solid electrolyte may be, for example, an argyrodite-type compound including at least one selected from Li6PS5Cl, Li6PS5Br, and Li6PS5I.

[0121] The argyrodite-type solid electrolyte may have a density of about 1.5 g / cc to about 2.0 g / cc. Since the argyrodite-type solid electrolyte has a density of 1.5 g / cc or more, it is possible to reduce the internal resistance of the all-solid-state secondary battery and effectively inhibit Li from penetrating the solid electrolyte layer.

[0122] The form of the sulfide-based solid electrolyte may be, for example, a particle form. Since the sulfide-based solid electrolyte has a particle form, the sulfide-based solid electrolyte can be easily mixed with the composite positive electrode active material particles.

[0123] The sulfide solid electrolyte may include, for example, a first sulfide solid electrolyte and a second sulfide solid electrolyte. For example, the first sulfide solid electrolyte and the second sulfide solid electrolyte may have different particle sizes. Since the sulfide solid electrolyte includes a first sulfide solid electrolyte and a second sulfide solid electrolyte having different particle sizes, the sulfide solid electrolyte may be more densely arranged between the composite positive electrode active material particles, thereby further improving the ion conductivity of the positive electrode. The first sulfide solid electrolyte may, for example, be a large-diameter sulfide solid electrolyte having a particle size larger than that of the second sulfide solid electrolyte, and the second sulfide solid electrolyte may, for example, be a small-diameter sulfide solid electrolyte having a particle size smaller than that of the first sulfide solid electrolyte. In the particle size distribution of the sulfide solid electrolyte, for example, the sulfide solid electrolyte may have a bimodal particle size distribution having a first peak corresponding to the first sulfide solid electrolyte and a second peak corresponding to the second sulfide solid electrolyte. The particle size ratio of the first sulfide solid electrolyte to the second sulfide solid electrolyte may be in the range of about 2: 1 to about 10: 1, about 2: 1 to about 6: 1, or about 2: 1 to about 4: 1. Since the first sulfide solid electrolyte and the second sulfide solid electrolyte have a particle size ratio in such a range, the ionic conductivity of the positive electrode including the sulfide solid electrolyte can be further improved. The first sulfide solid electrolyte may have a particle size of, for example, about 1 μm to about 10 μm, about 2 μm to about 6 μm, or about 2 μm to about 4 μm. The second sulfide solid electrolyte may have a particle size of, for example, about 0.1 μm to about 2 μm, about 0.5 μm to about 2 μm, or about 0.5 μm to about 1.5 μm. Since the first sulfide solid electrolyte and the second sulfide solid electrolyte each have a particle size in such a range, the first sulfide solid electrolyte and the second sulfide solid electrolyte may be densely filled in the positive electrode active material layer. Therefore, the ionic conductivity of the positive electrode including the sulfide solid electrolyte can be further improved. The weight ratio of the first sulfide solid electrolyte to the second sulfide solid electrolyte can be in the range of about 50:50 to about 90:10, about 60:40 to about 80:20, or about 70:30 to about 80:20. Since the first sulfide solid electrolyte and the second sulfide solid electrolyte have a weight ratio in such a range, the first sulfide solid electrolyte and the second sulfide solid electrolyte can densely fill the positive electrode active material layer. Therefore, the ionic conductivity of the positive electrode including the sulfide solid electrolyte can be further improved.

[0124] The solid electrolyte included in the positive electrode active material layer 12 may have a particle size smaller than that of the solid electrolyte included in the solid electrolyte layer 30. For example, the particle size of the solid electrolyte included in the positive electrode active material layer 12 may be 100%, 99% or less, 95% or less, 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, or 20% or less of the particle size of the solid electrolyte included in the solid electrolyte layer 30.

[0125] [Positive electrode: binder]

[0126] The positive electrode active material layer 12 may further include a binder. The binder may include, for example, styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc., but one or more embodiments are not necessarily limited thereto. Any material used as a binder in the art may be used. The binder may include, for example, a fluorine-based binder. The fluorine-based binder may be a binder including fluorine atoms. The fluorine-based binder may include, for example, polytetrafluoroethylene, polyvinylidene fluoride, etc. The binder may be omitted.

[0127] [Positive electrode: conductive material]

[0128] The positive electrode active material layer 12 may further include a conductive material. The conductive material may include a fibrous conductive material, a granular conductive material, or a combination thereof. The conductive material may include, for example, graphite, carbon black (CB), acetylene black (AB), Ketjen black (KB), carbon fiber, carbon nanotube, carbon nanofiber, metal powder, etc., but one or more embodiments are not necessarily limited thereto. Any material used as a conductive material in the art may be used. The conductive material may be omitted.

[0129] [Positive electrode: other additives]

[0130] In addition to the above-mentioned composite positive electrode active material and solid electrolyte, for example, the positive electrode active material layer 12 may further include additives such as a filler, a coating agent, a dispersant, and an ion conduction aid.

[0131] As the filler, coating agent, dispersant, and ion conduction aid that may be included in the positive electrode active material layer 12 , known materials generally used in electrodes of all-solid-state secondary batteries may be used.

[0132] [Positive electrode: positive electrode current collector]

[0133] The positive electrode current collector 11 may include a plate, foil, etc. made of, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel (SUS), titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof. The positive electrode current collector 11 may be omitted. The positive electrode current collector 11 may have a thickness of, for example, about 1 μm to about 100 μm, about 1 μm to about 50 μm, about 5 μm to about 25 μm, or about 10 μm to about 20 μm. The positive electrode current collector may include, for example, a base film and a metal layer disposed on one or both sides of the base film. The base film may include, for example, a polymer. The polymer may be, for example, a thermoplastic polymer. The polymer may be, for example, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or any combination thereof. The polymer may be an insulator. Because the substrate film includes an insulating thermoplastic polymer, the substrate film softens or liquefies in the event of a short circuit to prevent the operation of the battery, so that the rapid increase of the current can be suppressed. The metal layer may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge) or any alloy thereof. The metal layer is used as an electrochemical fuse and is cut off by overcurrent to prevent short circuit. By controlling the thickness of the metal layer, the limiting current and the maximum current can be adjusted. The metal layer can be plated or deposited on the substrate film. Due to the reduction in the thickness of the metal layer, the limiting current and / or the maximum current of the positive electrode current collector are reduced, so that the stability of the lithium battery can be improved in the event of a short circuit. A lead tab can be added to the metal layer for connection to the outside. The lead tab can be welded to the metal layer or the metal layer / substrate film stacking structure by ultrasonic welding, laser welding, spot welding, etc. While the substrate film and / or the metal layer are melted during welding, the metal layer can be electrically connected to the lead tab. For a stronger welding between the metal layer and the lead tab, a metal sheet may be further added between the metal layer and the lead tab. The metal sheet may be a thin sheet of the same material as the metal of the metal layer. The metal sheet may be, for example, a metal foil and a metal mesh. The metal sheet may be, for example, an aluminum foil, a copper foil, and a SUS foil. By performing welding after the metal sheet is disposed on the metal layer, the lead tab may be welded to the metal sheet / metal layer stacking structure or the metal sheet / metal layer / base film stacking structure. When the base film, the metal layer, and / or the metal sheet melt during welding, the metal layer or the metal layer / metal sheet stacking structure may be electrically connected to the lead tab. The metal sheet and / or the lead tab may also be added to the metal layer. The base film may have, for example, a thickness of 1 μm to 50 μm, 1.5 μm to 50 μm, 1.5 μm to 40 μm, or 1 μm to 30 μm. When the thickness of the base film is within the above range, the weight of the electrode assembly may be more effectively reduced.The melting point of the base film may be, for example, 100°C to 300°C, 100°C to 250°C, or 100°C to 200°C. Because the base film has a melting point within the above range, the base film melts during the process of welding the lead tab to easily bond to the lead tab. In order to improve the adhesion between the base film and the metal layer, a surface treatment such as a corona treatment may be performed on the base film. The thickness of the metal layer may be, for example, 0.01 μm to 3 μm, 0.1 μm to 3 μm, 0.1 μm to 2 μm, or 0.1 μm to 1 μm. When the thickness of the metal layer is within the above range, the stability of the electrode assembly may be obtained while maintaining the conductivity of the electrode assembly. The thickness of the metal sheet may be, for example, 2 μm to 10 μm, 2 μm to 7 μm, or 4 μm to 6 μm. When the thickness of the metal sheet is within the above range, the metal layer may be more easily connected to the lead tab. Since the positive electrode current collector has the above structure, the weight of the positive electrode can be reduced, so that the energy density of the positive electrode and the lithium battery can be increased.

[0134] [All-solid-state secondary battery]

[0135] The all-solid-state secondary battery includes a positive electrode, a negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode. The electrolyte layer includes an electrolyte. The electrolyte may include, for example, a solid electrolyte, a gel electrolyte, or a combination thereof.

[0136] Reference Figure 4 and Figure 5 The all-solid-state secondary battery 1 according to the embodiment may include the above-described positive electrode 10 , the negative electrode 20 , and a solid electrolyte layer 30 disposed between the positive electrode 10 and the negative electrode 20 .

[0137] Since the all-solid-state secondary battery 1 includes the above-described positive electrode 10 , the cycle characteristics of the all-solid-state secondary battery 1 can be improved.

[0138] [Solid electrolyte layer]

[0139] [Solid electrolyte layer: solid electrolyte]

[0140] The solid electrolyte layer 30 may include a solid electrolyte disposed between the positive electrode 10 and the negative electrode 20 , and may include a solid electrolyte.

[0141] The solid electrolyte may be, for example, a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a polymer solid electrolyte, or any combination thereof.

[0142] The solid electrolyte included in the solid electrolyte layer 30 may be selected, for example, from sulfide solid electrolytes included in the above positive electrode. For specific details of the solid electrolyte, refer to the above positive electrode. Optionally, the solid electrolyte layer 30 may include an oxide solid electrolyte. The oxide solid electrolyte may include, for example, those selected from Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (where 0 < x < 2 and 0 ≤ y < 3), BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3 (PLZT) (where 0 ≤ x < 1 and 0 ≤ y < 1), Pb(Mg3Nb 2 / 3 )O3 - PbTiO3 (PMN - PT), HfO2, SrTiO3, SnO2, CeO2, Na2O, MgO, NiO, CaO, BaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiO2, Li3PO4, Li x Ti y (PO4)3 (where 0 < x < 2 and 0 < y < 3), Li x Al y Ti z (PO4)3 (where 0 < x < 2, 0 < y < 1 and 0 < z < 3), Li 1+x+y (Al,Ga) x (Ti,Ge) 2-x Si y P 3-y O 12 (where 0 ≤ x ≤ 1 and 0 ≤ y ≤ 1), Li x La y TiO3 (where 0 < x < 2 and 0 < y < 3), Li2O, LiOH, Li2CO3, LiAlO2, Li2O - Al2O3 - SiO2 - P2O5 - TiO2 - GeO2 and Li 3+x La3M2O 12 (where M = Te, Nb or Zr and 0 ≤ x ≤ 10), at least one of which. The solid electrolyte is manufactured by a sintering method or the like. For example, the oxide solid electrolyte is selected from Li7La3Zr2O 12 (LLZO) and Li 3+x La3Zr 2- a M a O 12(M-doped LLZO) (where M = Ga, W, Nb, Ta, or Al, 0 < a < 2, and 0 ≤ x ≤ 10), a garnet-type solid electrolyte. The solid electrolyte included in the solid electrolyte layer 30 may have a larger particle size than the solid electrolyte included in the positive electrode active material layer 12. For example, the particle size of the solid electrolyte included in the solid electrolyte layer 30 may be 100%, 101% or more, 105% or more, 110% or more, 120% or more, 130% or more, 140% or more, 150% or more, 200% or more, 300% or more, or 400% or more of the particle size of the solid electrolyte included in the positive electrode active material layer 12. The solid electrolyte layer 30 may include, for example, a polymer solid electrolyte. The polymer solid electrolyte may include, for example, a mixture of a lithium salt and a polymer or a polymer having an ion-conductive functional group. The polymer solid electrolyte may be, for example, a polymer electrolyte in a solid state at 25 °C and 1 atm. For example, the polymer solid electrolyte may not include a liquid. The polymer solid electrolyte includes a polymer, examples of which include polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene (PVDF-HFP), poly(styrene-b-ethylene oxide) block copolymer (PS-PEO), poly(styrene-butadiene), poly(styrene-isoprene-styrene), poly(styrene-b-divinylbenzene) block copolymer, poly(styrene-ethylene oxide-styrene) block copolymer, polystyrene sulfonate (PSS), polyvinyl fluoride (PVF), poly(methyl methacrylate) (PMMA), polyethylene glycol (PEG), polyacrylonitrile (PAN), polytetrafluoroethylene (PTFE), poly(3,4-ethylenedioxythiophene) (PEDOT), polypyrrole (PPY), polyaniline, polyacetylene, Nafion, Aquivion, Flemion, Gore, Aciplex, Morgane ADP, sulfonated poly(ether ether ketone) (SPEEK), sulfonated poly(arylene ether ketone ketone sulfone) (SPAEKKS), sulfonated poly(aryl ether ketone) (SPAEK), poly[bis(benzimidazole benzisoquinolinone)] (SPBIBI), poly(styrene sulfonic acid) (PSS), lithium 9,10-diphenylanthracene-2-sulfonate (DPASLi + ), or any combination thereof. However, the examples are not limited thereto, and any polymer electrolyte commonly available in the art may also be used. Any lithium salt commonly available in the art may also be used. Examples of the lithium salt may include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(Cy F 2y+1 SO2) (wherein x and y are each independently in the range of 1 to 20), LiCl, LiI or any mixture thereof. The polymer included in the polymer solid electrolyte may be, for example, a compound including 10 or more, 20 or more, 50 or more, or 100 or more repeating units. The weight average molecular weight of the polymer included in the polymer solid electrolyte may be, for example, 1000 Daltons (Da) or more, 10,000 Da or more, 100,000 Da or more, or 1,000,000 Da or more. The solid electrolyte layer 30 may include, for example, a gel electrolyte. The gel electrolyte is, for example, a polymer gel electrolyte. For example, the gel electrolyte may have a gel state without including a polymer. The polymer gel electrolyte may include, for example, a liquid electrolyte and a polymer, or an organic solvent and a polymer having an ion conductive functional group. The polymer gel electrolyte may be, for example, a polymer electrolyte that is in a gel state at 25° C. and 1 atm. The polymer gel electrolyte may have, for example, a gel state without including a liquid. The liquid electrolyte for the polymer gel electrolyte may be, for example: a mixture of an ionic liquid and a lithium salt; a mixture of a lithium salt and an organic solvent; a mixture of an ionic liquid and an organic solvent; or a mixture of a lithium salt, an ionic liquid and an organic solvent. The polymer for the polymer gel electrolyte may be selected from the polymer for the polymer solid electrolyte. The organic solvent may be selected from the organic solvent for the liquid electrolyte. The lithium salt may be selected from the lithium salt for the polymer solid electrolyte. The ionic liquid refers to a salt in a liquid state, and refers to a room temperature molten salt composed only of ions and having a melting point below room temperature. The ionic liquid may include, for example, at least one compound including: a) at least one cation selected from ammonium, pyrimidinium, pyridinium, pyrrolidinium, imidazolium, piperidinium, pyrazolium, oxazolium, pyridazinium, phosphonium, sulfonium, triazole and any mixture thereof; and b) selected from BF4 - PF6 - 、AsF6 - 、SbF6 - 、AlCl4 - 、HSO4 - 、ClO4 - 、CH3SO3 - CF3CO2 - , Cl - Br - ,I - 、BF4 - 、SO4 - CF3SO3 - 、(FSO2)2N - 、(C2F5SO2)2N - 、(C2F5SO2)(CF3SO2)N- and (CF3SO2)2N - At least one compound of at least one anion in the polymer solid electrolyte. For example, the polymer solid electrolyte can be impregnated with a liquid electrolyte in a secondary battery to form a polymer gel electrolyte. The polymer gel electrolyte may further include inorganic particles. The polymer included in the polymer gel electrolyte can be a compound including, for example, 10 or more, 20 or more, 50 or more, or 100 or more repeating units. The weight average molecular weight of the polymer included in the polymer gel electrolyte can be, for example, 500Da or more, 1000Da or more, 10,000Da or more, 100,000Da or more, or 1,000,000Da or more.

[0143] [Solid electrolyte layer: Binder]

[0144] The solid electrolyte layer 30 may include, for example, a binder. The binder of the solid electrolyte layer 30 may include, for example, SBR, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc., but one or more embodiments are not limited thereto. Any material used as a binder in the art may be used. The binder of the solid electrolyte layer 30 may be the same or different from the binder included in the positive electrode active material layer 12 and the first negative electrode active material layer 22. The binder may be omitted. Relative to the gross weight of the solid electrolyte layer 30, the content of the binder included in the solid electrolyte layer 30 may be, for example, in the range of about 0wt% to about 10wt%, about 0wt% to about 5wt%, about 0wt% to about 3wt%, about 0wt% to about 1wt%, about 0wt% to about 0.5wt%, or about 0wt% to 0.1wt%.

[0145] [Negative electrode]

[0146] [Negative electrode: negative electrode active material]

[0147] The first negative electrode active material layer 22 may include, for example, a negative electrode active material and a binder.

[0148] The negative electrode active material included in the first negative electrode active material layer 22 may have, for example, a particle form. The negative electrode active material having a particle form may have, for example, an average particle size of 4 μm or less, 3 μm or less, 2 μm or less, 1 μm or less, or 900 nm or less. The negative electrode active material having a particle form may have, for example, an average particle size of about 10 nm to 4 μm, about 10 nm to about 3 μm, about 10 nm to about 2 μm, about 10 nm to about 1 μm, or about 10 nm to about 900 nm. Since the negative electrode active material has an average particle size within such a range, reversible absorption and / or desorption of lithium can be more easily performed during charge / discharge. The average particle size of the negative electrode active material is, for example, a median particle size (D50) measured using a laser-type particle size distribution analyzer.

[0149] The negative electrode active material included in the first negative electrode active material layer 22 may include, for example, at least one selected from a carbon-based negative electrode active material and a metal or metalloid negative electrode active material.

[0150] The carbon-based negative electrode active material may specifically be amorphous carbon. Examples of amorphous carbon may include CB, AB, furnace black (FB), KB, graphene, etc., but one or more embodiments are not necessarily limited thereto. Any material classified as amorphous carbon in the art may be used. Amorphous carbon may be carbon that has no crystallinity or has very low crystallinity, and may be distinguished from crystalline carbon or graphite-based carbon.

[0151] The metal or metalloid negative electrode active material may include at least one selected from gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn) and zinc (Zn), but one or more embodiments are not necessarily limited thereto. Any material used as a metal negative electrode active material or a metalloid negative electrode active material in the art and forming an alloy or compound with lithium can be used. For example, nickel (Ni) does not form an alloy with lithium, so it is not a metal negative electrode active material.

[0152] The first negative electrode active material layer 22 may include one type of negative electrode active material among such negative electrode active materials or a mixture of multiple different negative electrode active materials. For example, the first negative electrode active material layer 22 may include only amorphous carbon or may include at least one selected from gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn) and zinc (Zn). Alternatively, the first negative electrode active material layer 22 may include a mixture of amorphous carbon and at least one selected from gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn) and zinc (Zn). The mixing ratio of the mixture of amorphous carbon and gold, etc. may be, for example, a weight ratio of about 10:1 to about 1:2, about 5:1 to about 1:1 or about 4:1 to about 2:1, but is not necessarily limited to such a range. The mixing ratio can be selected according to the characteristics required by the all-solid-state secondary battery 1. Since the negative electrode active material has such a composition, the cycle characteristics of the all-solid-state secondary battery 1 can be further improved.

[0153] The negative electrode active material included in the first negative electrode active material layer 22 may include, for example, a mixture of first particles containing amorphous carbon and second particles containing metals or metalloids. Examples of metals or metalloids may include gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), zinc (Zn), etc. Alternatively, the metalloid may be a semiconductor. Relative to the total weight of the mixture, the content of the second particles may be in the range of about 8wt% to about 60wt%, about 10wt% to about 50wt%, about 15wt% to about 40wt%, or about 20wt% to about 30wt%. Since the second particles are included in such a range of contents, the cycle characteristics of the all-solid-state secondary battery 1 may be further improved, for example.

[0154] [Negative electrode: binder]

[0155] The binder included in the first negative electrode active material layer 22 may include, for example, SBR, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile, polymethyl methacrylate, etc., but one or more embodiments are not necessarily limited thereto. Any material used as a binder in the art may be used. The binder may be provided as a single binder or a plurality of different binders.

[0156] Since the first negative electrode active material layer 22 includes a binder, the first negative electrode active material layer 22 can be stably attached to the negative electrode current collector 21. In addition, although the volume and / or relative position of the first negative electrode active material layer 22 changes during charge / discharge, the first negative electrode active material layer 22 can be suppressed from being broken. For example, if the first negative electrode active material layer 22 does not include a binder, the first negative electrode active material layer 22 can be easily separated from the negative electrode current collector 21. At the portion of the negative electrode current collector 21 exposed by the separation of the first negative electrode active material layer 22 from the negative electrode current collector 21, the negative electrode current collector 21 will contact the solid electrolyte layer 30, so the possibility of short circuit will increase. For example, a slurry in which a material constituting the first negative electrode active material layer 22 is dispersed can be applied to the negative electrode current collector 21 and dried to prepare the first negative electrode active material layer 22. Since the binder is included in the first negative electrode active material layer 22, the negative electrode active material can be stably dispersed in the slurry. For example, if the slurry is applied to the negative electrode current collector 21 by screen printing, clogging of the screen (eg, clogging due to aggregates of the negative electrode active material) can be suppressed.

[0157] [Negative electrode: other additives]

[0158] The first negative electrode active material layer 22 may further include, for example, additives included in the existing all-solid-state secondary battery 1 , such as a filler, a coating agent, a dispersant, and an ion conduction aid.

[0159] [Negative electrode: first negative electrode active material layer]

[0160] The thickness of the first negative electrode active material layer 22 may be, for example, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or 5% or less of the thickness of the positive electrode active material layer 12. The first negative electrode active material layer 22 may have a thickness of, for example, about 1 μm to about 20 μm, about 2 μm to about 10 μm, or about 3 μm to about 7 μm. If the first negative electrode active material layer 22 is too thin, the lithium dendrites formed between the first negative electrode active material layer 22 and the negative electrode current collector 21 may collapse the first negative electrode active material layer 22, which may make it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1. If the thickness of the first negative electrode active material layer 22 is excessively increased, the energy density of the all-solid-state secondary battery 1 may be reduced and the internal resistance of the all-solid-state secondary battery 1 may be increased due to the first negative electrode active material layer 22, which may make it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1.

[0161] If the thickness of the first negative electrode active material layer 22 is reduced, for example, the charge capacity of the first negative electrode active material layer 22 may also be reduced. The charge capacity of the first negative electrode active material layer 22 may be, for example, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, 5% or less, or 2% or less of the charge capacity of the positive electrode active material layer 12. The charge capacity of the first negative electrode active material layer 22 may be, for example, in the range of about 0.1% to about 50%, about 0.1% to about 40%, about 0.1% to about 30%, about 0.1% to about 20%, about 0.1% to about 10%, about 0.1% to about 5%, or about 0.1% to about 2% of the charge capacity of the positive electrode active material layer 12. If the charge capacity of the first negative electrode active material layer 22 is too low, since the first negative electrode active material layer 22 becomes very thin, lithium dendrites formed between the first negative electrode active material layer 22 and the negative electrode current collector 21 during repeated charge / discharge processes may collapse the first negative electrode active material layer 22, which may make it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1. If the charge capacity of the first negative electrode active material layer 22 is excessively increased, the energy density of the all-solid-state secondary battery 1 may be reduced and the internal resistance of the all-solid-state secondary battery 1 may be increased due to the first negative electrode active material layer 22, which may make it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1.

[0162] The charge capacity of the positive electrode active material layer 12 is obtained by multiplying the charge capacity density (mAh / g) of the positive electrode active material by the mass of the positive electrode active material in the positive electrode active material layer 12. If a plurality of positive electrode active materials are used, the value of the charge capacity density × mass is calculated for each positive electrode active material, and the sum of the values ​​is the charge capacity of the positive electrode active material layer 12. The charge capacity of the first negative electrode active material layer 22 is also calculated in the same manner. That is, the charge capacity of the first negative electrode active material layer 22 is obtained by multiplying the charge capacity density (mAh / g) of the negative electrode active material by the mass of the negative electrode active material in the first negative electrode active material layer 22. If a plurality of negative electrode active materials are used, the value of the charge capacity density × mass is calculated for each negative electrode active material, and the sum of the values ​​is the charge capacity of the first negative electrode active material layer 22. Here, the charge capacity density of the positive electrode active material and the negative electrode active material is the capacity estimated using an all-solid-state half-cell using lithium metal as a counter electrode. Here, the charge capacity of the positive electrode active material layer 12 and the first negative electrode active material layer 22 is directly measured by measuring the charge capacity using an all-solid-state half-cell. If the measured charge capacity is divided by the mass of each active material, the charge capacity density is obtained. Alternatively, the charge capacity of the positive electrode active material layer 12 and the first negative electrode active material layer 22 may be the initial charge capacity measured during the first cycle of charging.

[0163] [Negative electrode: second negative electrode active material layer]

[0164] Although not shown in the drawings, the all-solid-state secondary battery 1 may further include, for example, a second negative electrode active material layer disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22 by charging. The second negative electrode active material layer may be a metal layer including lithium or a lithium alloy. The metal layer may include lithium or a lithium alloy. Therefore, since the second negative electrode active material layer is a metal layer including lithium, the second negative electrode active material layer may be used as, for example, a lithium reservoir. Examples of lithium alloys may include Li-Al alloys, Li-Sn alloys, Li-In alloys, Li-Ag alloys, Li-Au alloys, Li-Zn alloys, Li-Ge alloys, Li-Si alloys, etc., but one or more embodiments are not limited thereto. Any material used as a lithium alloy in the art may be used. The second negative electrode active material layer may be made of one of the alloys or lithium, or may be made of multiple types of alloys. The second negative electrode active material layer may be, for example, a plated layer. The second negative electrode active material layer may, for example, be plated between the first negative electrode active material layer 22 and the negative electrode current collector 21 during the charging process of the all-solid-state secondary battery 1.

[0165] The second negative electrode active material layer may have a thickness of, for example, about 1 μm to about 1,000 μm, about 1 μm to about 500 μm, about 1 μm to about 200 μm, about 1 μm to about 150 μm, about 1 μm to about 100 μm, or about 1 μm to about 50 μm, but one or more embodiments are not particularly limited thereto. If the second negative electrode active material layer is too thin, the second negative electrode active material layer is difficult to use as a lithium storage device. If the second negative electrode active material layer is too thick, the mass and volume of the all-solid-state secondary battery 1 may increase, and its cycle characteristics may deteriorate. The second negative electrode active material layer may be, for example, a metal foil having a thickness within such a range.

[0166] In the all-solid-state secondary battery 1, the second negative electrode active material layer may be disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22, for example, before assembling the all-solid-state secondary battery 1, or may be plated between the negative electrode current collector 21 and the first negative electrode active material layer 22 by charging after assembling the all-solid-state secondary battery 1. If the second negative electrode active material layer 23 is disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22 before assembling the all-solid-state secondary battery 1, the second negative electrode active material layer 23 may be a metal layer including lithium, and thus may be used as a lithium storage. For example, before assembling the all-solid-state secondary battery 1, a lithium foil may be disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22. As a result, the cycle characteristics of the all-solid-state secondary battery 1 including the second negative electrode active material layer can be further improved. If the second negative electrode active material layer is plated by charging after assembling the all-solid-state secondary battery 1, since the second negative electrode active material layer is not included when assembling the all-solid-state secondary battery 1, the energy density of the all-solid-state secondary battery 1 may be increased. For example, during charging of the all-solid-state secondary battery 1, the first negative electrode active material layer 22 is charged with a charge capacity exceeding that of the first negative electrode active material layer 22. That is, the first negative electrode active material layer 22 is overcharged. At the start of charging, lithium is absorbed by the first negative electrode active material layer 22. The negative electrode active material included in the first negative electrode active material layer 22 may form an alloy or compound with lithium ions transferred from the positive electrode 10. For example, if the first negative electrode active material layer 22 is charged with a capacity exceeding that of the first negative electrode active material layer 22, lithium may be plated on the rear surface of the first negative electrode active material layer 22 (ie, between the negative electrode current collector 21 and the first negative electrode active material layer 22), and due to the plated lithium, a metal layer corresponding to the second negative electrode active material layer may be formed. The second negative electrode active material layer may be a metal layer mainly made of lithium (ie, metallic lithium). Such a result is obtained if the negative electrode active material included in the first negative electrode active material layer 22 includes, for example, a material that forms an alloy or compound with lithium. During discharge, lithium in the first negative electrode active material layer 22 and the second negative electrode active material layer (ie, metal layer) can be ionized to move toward the positive electrode 10. Therefore, lithium can be used as a negative electrode active material in the all-solid-state secondary battery 1. In addition, since the first negative electrode active material layer 22 covers the second negative electrode active material layer, the first negative electrode active material layer 22 can be used as a protective layer for the second negative electrode active material layer (ie, metal layer), and at the same time, the precipitation growth of lithium dendrites can be suppressed. Therefore, the short circuit and capacity reduction of the all-solid-state secondary battery 1 can be suppressed, and as a result, the cycle characteristics of the all-solid-state secondary battery 1 can be improved.In addition, if the second negative electrode active material layer is set by charging after assembling the all-solid-state secondary battery 1, the negative electrode current collector 21, the first negative electrode active material layer 22, and the area therebetween can all be Li-free areas that do not include lithium (Li), for example, in the initial state of the all-solid-state secondary battery or in the state after discharge of the all-solid-state secondary battery.

[0167] [Negative electrode: negative electrode current collector]

[0168] The negative electrode current collector 21 may be made of, for example, a material that does not react with lithium (i.e., does not form both alloys and compounds with lithium). Examples of materials constituting the negative electrode current collector 21 may include copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), etc., but one or more embodiments are not necessarily limited thereto. Any material used as an electrode current collector in the art may be used. The negative electrode current collector 21 may be made of, for example, an alloy or a covering material of one or two or more of the above-mentioned metals. The negative electrode current collector 21 may be in the form of, for example, a plate or foil.

[0169] The all-solid-state secondary battery 1 may also include, for example, a thin film containing an element capable of forming an alloy with lithium on the negative electrode current collector 21. The thin film may be disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22. The thin film may include an element capable of forming an alloy with, for example, lithium. Examples of elements capable of forming an alloy with lithium may include gold, silver, zinc, tin, indium, silicon, aluminum, bismuth, and the like, but one or more embodiments are not necessarily limited thereto. Any element capable of forming an alloy with lithium in the art may be used. The thin film may be made of an alloy of one or more metals in the metal. For example, since the thin film is disposed on the negative electrode current collector 21, the second negative electrode active material layer in the form of a plating, for example, between the thin film and the first negative electrode active material layer 22, may be further flattened, and the cycle characteristics of the all-solid-state secondary battery 1 may be further improved.

[0170] The film may have a thickness of, for example, about 1 nm to about 800 nm, about 10 nm to about 700 nm, about 50 nm to about 600 nm, or about 100 nm to about 500 nm. If the thickness of the film is less than about 1 nm, it may be difficult to show the function of the film. If the film is too thick, the film itself may absorb lithium to reduce the amount of lithium plated at the negative electrode, which may reduce the energy density of the all-solid-state battery and may degrade the cycle characteristics of the all-solid-state secondary battery 1. The film may be disposed on the negative electrode current collector 21 by, for example, vacuum deposition, sputtering, plating, etc., but one or more embodiments are not necessarily limited to such a method. Any method capable of forming a film in the art may be used.

[0171] Although not shown in the drawings, the negative electrode current collector 21 may include, for example, a base film and a metal layer disposed on one or both sides of the base film. The base film may include, for example, a polymer. The polymer may be, for example, a thermoplastic polymer. The polymer may be, for example, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI) or any combination thereof. The polymer may be an insulating polymer. Because the base film includes an insulating thermoplastic polymer, the base film softens or liquefies in the event of a short circuit to block the operation of the battery, so that the rapid increase of the current can be suppressed. The metal layer may include, for example, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni) or an alloy thereof. The metal layer may correspond to, for example, a first metal substrate. The metal layer may also include a coating layer comprising a second metal. The negative electrode current collector 21 may further include a metal sheet and / or a lead tab. The negative electrode current collector 21 has a more detailed description of the base film, metal layer, metal sheet, and lead tab. Because the negative electrode current collector 21 has the above structure, the weight of the negative electrode can be reduced, and thus the energy density of the negative electrode and the lithium battery can be increased.

[0172] [Positive electrode]

[0173] The above-described positive electrode can be used without any change.

[0174] [Positive electrode layer: inactive member]

[0175] Reference Figure 6 and Figure 7 The positive electrode 10 may include a positive electrode current collector 11 , a positive electrode active material layer 12 disposed on one surface of the positive electrode current collector 11 , and an inactive member 40 may be further disposed on one surface of the positive electrode 10 .

[0176] Since the inactive member 40 is included, the solid electrolyte layer 30 can be prevented from being broken during the manufacture and / or charge / discharge of the all-solid-state secondary battery 1, thereby improving the cycle characteristics of the all-solid-state secondary battery 1. In the all-solid-state secondary battery 1 that does not include the inactive member 40, during the manufacture and / or charge / discharge of the all-solid-state secondary battery 1, uneven pressure may be applied to the solid electrolyte layer 30 in contact with the positive electrode 10, and thus cracks may be generated in the solid electrolyte layer 30, and the possibility of a short circuit may be increased due to the growth of lithium metal through the cracks.

[0177] The inactive member 40 may surround a portion or all of the side surface of the positive electrode 10, and may be in contact with the solid electrolyte layer 30. Since the inactive member 40 surrounds the side surface of the positive electrode 10 and is in contact with the solid electrolyte layer 30, in the solid electrolyte layer 30 that is not in contact with the positive electrode 10, it is possible to effectively suppress the solid electrolyte layer 30 from being broken due to the pressure difference during the pressing process. The inactive member 40 may surround the side surface of the positive electrode 10, and more specifically may be separated from the negative electrode 20, and more specifically, may be separated from the first negative electrode active material layer 22. The inactive member 40 may surround the side surface of the positive electrode 10, may be in contact with the solid electrolyte layer 30, and may be separated from the negative electrode 20. Therefore, the possibility of a short circuit due to physical contact between the positive electrode 10 and the first negative electrode active material layer 22 or a short circuit due to overcharging of lithium can be suppressed. Reference Figure 6 , the inactive member 40 may be disposed on one side surface of the positive electrode active material layer 12 and may also be disposed on one side surface of the positive electrode current collector 11 at the same time, thereby more effectively suppressing the possibility of a short circuit due to contact between the positive electrode current collector 11 and the negative electrode 20. Alternatively, referring to Figure 7 , the inactive member 40 may be disposed on one side surface of the positive electrode active material layer 12, and may be disposed between the solid electrolyte layer 30 and the positive electrode current collector 11 opposite to the solid electrolyte layer 30. The inactive member 40 may not be disposed on one side surface of the positive electrode current collector 11. Since the inactive member 40 is disposed between the positive electrode current collector 11 and the solid electrolyte layer 30, a short circuit caused by contact between the positive electrode current collector 11 and the negative electrode 20 can be effectively prevented.

[0178] Reference Figure 6 and Figure 7 , the inactive member 40 may extend from one side surface of the positive electrode 10 to the end of the solid electrolyte layer 30. Since the inactive member 40 extends to the end of the solid electrolyte layer 30, it is possible to suppress the occurrence of cracks at the end of the solid electrolyte layer 30. The end of the solid electrolyte layer 30 may be the outermost portion in contact with the side surface of the solid electrolyte layer 30. The inactive member 40 may extend to the outermost portion in contact with the side surface of the solid electrolyte layer 30. The inactive member 40 may be separated from the negative electrode 20, and more specifically, may be separated from the first negative electrode active material layer 22. The inactive member 40 may extend to the end of the solid electrolyte layer 30, and may not be in contact with the negative electrode 20. The inactive member 40 may fill a space extending from one side surface of the positive electrode 10 to the end of the solid electrolyte layer 30, for example.

[0179] Inactive member 40 may be, for example, a gasket. Since a gasket is used as inactive member 40, cracks occurring in solid electrolyte layer 30 due to a pressure difference during a pressing process can be effectively suppressed.

[0180] The inactive member 40 may have, for example, a single-layer structure. Alternatively, although not shown in the drawings, the inactive member 40 may have a multilayer structure. In the inactive member 40 having a multilayer structure, each layer may have a different composition. The inactive member 40 having a multilayer structure may have, for example, a two-layer structure, a three-layer structure, a four-layer structure, or a five-layer structure. The inactive member 40 having a multilayer structure may include, for example, one or more adhesive layers and one or more supporting layers. For example, the adhesive layer may effectively prevent the separation between the positive electrode 10 and the solid electrolyte layer 30 due to the volume change of the positive electrode 10 occurring during the charging / discharging process of the all-solid-state secondary battery 1, and may provide a bonding force between the supporting layer and other layers to improve the film strength of the inactive member 40. The supporting layer may provide a supporting force to the inactive member 40, may prevent the non-uniformity of the pressure applied to the solid electrolyte layer 30 during the pressing process or the charging / discharging process, and may prevent the shape deformation of the manufactured all-solid-state secondary battery 1.

[0181] Reference Figure 8, the all-solid-state secondary battery 1 may include a positive electrode 10, a negative electrode 20, and a solid electrolyte layer 30 disposed therebetween, wherein the positive electrode 10 includes a positive electrode current collector 11 and each of a first positive electrode active material layer 12a and a second positive electrode active material layer 12b disposed on both surfaces of the positive electrode current collector 11, the solid electrolyte layer 30 includes each of a first solid electrolyte layer 30a in contact with the first positive electrode active material layer 12a and a second solid electrolyte layer 30b in contact with the second positive electrode active material layer 12b, the negative electrode 20 includes each of a first negative electrode layer 20a in contact with the first solid electrolyte layer 30a and a second negative electrode layer 20b in contact with the second solid electrolyte layer 30b, and a first inactive member 40 is disposed around a side surface of the positive electrode 10 between the first solid electrolyte layer 30a and the second solid electrolyte layer 30b facing each other. The first inactive member 40 may include, for example, a 1a inactive member 40a in contact with the first solid electrolyte layer 30a and a 1b inactive member 40b in contact with the second solid electrolyte layer 30b. Therefore, the all-solid-state secondary battery 1 can have a dual-cell structure. Since the all-solid-state secondary battery 1 has such a dual-cell structure, the solid electrolyte layer 30 and the negative electrode 20 are each arranged to be symmetrical and opposite to the positive electrode 10, thereby more effectively suppressing the structural deformation caused by the pressure applied during the manufacture of the all-solid-state secondary battery 1. Therefore, the solid electrolyte layer 30 can be suppressed from rupturing during the manufacturing process and / or charging / discharging process of the all-solid-state secondary battery 1, and the short circuit of the all-solid-state secondary battery 1 caused by cracks can be prevented, thereby further improving the cycle characteristics of the all-solid-state secondary battery 1. In addition, the multiple positive electrode active material layers 12a, 12b use only one positive electrode current collector 11, so the energy density of the all-solid-state secondary battery 1 can be increased.

[0182] Reference Figures 6 to 8 , the inactive member 40 may be, for example, a flame retardant inactive member. The flame retardant inactive member may provide flame retardancy, so that the possibility of thermal runaway and fire of the all-solid-state secondary battery 1 may be prevented. As a result, the safety of the all-solid-state secondary battery 1 may be further improved. The flame retardant inactive member may absorb residual moisture in the all-solid-state secondary battery 1, and thus the degradation of the all-solid-state secondary battery 1 may be prevented, thereby improving the life characteristics of the all-solid-state secondary battery 1.

[0183] The flame retardant inactive member may include, for example, a matrix and a filler. The matrix may include, for example, a substrate and a reinforcing material. The matrix may include, for example, a fiber substrate and a fiber reinforcing material. Since the matrix includes a substrate, the matrix may have elasticity. Therefore, the matrix can effectively accommodate the volume change of the all-solid-state secondary battery 1 during charge / discharge, and may be set in one of various positions. The substrate included in the matrix may include, for example, a first fiber material. Since the substrate includes the first fiber material, it is possible to effectively adapt to the volume change of the positive electrode active material layer 12 caused during the charge / discharge process of the all-solid-state secondary battery 1, and effectively suppress the deformation of the inactive member 40 caused by the volume change of the positive electrode active material layer 12. The first fiber material may be, for example, a material having an aspect ratio of 5 or more, 20 or more, or 50 or more. The first fiber material may be, for example, a material having an aspect ratio of about 5 to about 1,000, about 20 to about 1,000, or about 50 to about 1,000. The first fiber material may be, for example, an insulating material. Since the first fiber material is an insulating material, it is possible to effectively prevent a short circuit between the positive electrode 10 and the negative electrode 20 caused by lithium dendrites generated during the charge / discharge of the all-solid-state secondary battery 1. The first fiber material may include, for example, at least one selected from pulp fibers, insulating polymer fibers, and ion conductive polymer fibers. Since the matrix includes a reinforcing material, the strength of the matrix can be improved. Therefore, the matrix can prevent excessive volume changes during the charge / discharge of the all-solid-state secondary battery 1, and can prevent deformation of the all-solid-state secondary battery 1. The reinforcing material included in the matrix may include, for example, a second fiber material. Since the reinforcing material includes the second fiber material, the strength of the matrix can be increased more uniformly. The second fiber material may be, for example, a material having an aspect ratio of 3 or more, 5 or more, or 10 or more. The first fiber material may be, for example, a material having an aspect ratio of about 3 to about 100, about 5 to about 100, or about 10 to about 100. The second fiber material may be, for example, a flame retardant material. Since the second fiber material is a flame retardant material, it is possible to effectively suppress ignition caused by external impact or thermal runaway occurring during the charge / discharge process of the all-solid-state secondary battery 1. The second fiber material may be, for example, glass fiber, metal oxide fiber, ceramic fiber, or the like.

[0184] The flame retardant inactive member may include a filler in addition to the matrix. The filler may be disposed inside the matrix, may be deposited on the surface of the matrix, or may be disposed inside and on the surface. The filler may be, for example, an inorganic material. The filler included in the flame retardant inactive member may be, for example, a hygroscopic agent. The filler may adsorb moisture at a temperature of, for example, less than 100°C to remove moisture remaining in the all-solid-state secondary battery 1 and prevent degradation of the all-solid-state secondary battery 1. In addition, if the temperature of the all-solid-state secondary battery 1 increases to 150°C or more due to thermal runaway caused by external impact or during the charging / discharging process of the all-solid-state secondary battery 1, the filler may release the adsorbed moisture to effectively suppress the ignition of the all-solid-state secondary battery 1. That is, the filler may be, for example, a flame retardant material. The filler may include, for example, a metal hydroxide having moisture adsorption properties. The metal hydroxide included in the filler may include, for example, Mg(OH)2, Fe(OH)3, Sb(OH)3, Sn(OH)4, TI(OH)3, Zr(OH)4, Al(OH)3, or a combination thereof. The content of the filler included in the flame retardant inactive member can be, for example, about 10 parts by weight to about 80 parts by weight, about 20 parts by weight to about 80 parts by weight, about 30 parts by weight to about 80 parts by weight, about 40 parts by weight to about 80 parts by weight, about 50 parts by weight to about 80 parts by weight, about 60 parts by weight to about 80 parts by weight, or about 65 parts by weight to about 80 parts by weight relative to about 100 parts by weight of the flame retardant inactive member.

[0185] The flame retardant inactive member may further include, for example, a binder. The binder may include, for example, a curable polymer or a non-curable polymer. The curable polymer may be a polymer cured by heat and / or pressure. The curable polymer may be, for example, a solid at room temperature. The flame retardant inactive member may include, for example, a thermosetting film and / or a cured product thereof. The thermosetting polymer may be, for example, TSA-66 manufactured by Toray Industries, Inc.

[0186] In addition to the above-mentioned substrate, reinforcing material, filler and binder, the flame retardant inactive component may further include other materials. For example, the flame retardant inactive component may also include at least one selected from paper, insulating polymer, ion conductive polymer, insulating inorganic material, oxide solid electrolyte and sulfide solid electrolyte. The insulating polymer may be, for example, an olefin polymer, such as polypropylene (PP) or polyethylene (PE).

[0187] The density of the substrate or the density of the reinforcing material included in the flame retardant inactive member can be, for example, in the range of about 10% to about 300%, about 10% to about 150%, about 10% to about 140%, about 10% to about 130% or about 10% to about 120% of the density of the positive electrode active material included in the positive electrode active material layer 12.

[0188] The inactive member 40 may be a member that does not include an electrochemically active material (e.g., an electrode active material). The electrode active material may be a material that absorbs / desorbs lithium. The first inactive member 40 may be a member made of a material used in the art other than the electrode active material.

[0189] A method for preparing a positive electrode according to another embodiment may include mixing a composite positive electrode active material and a sulfide-based solid electrolyte.

[0190] A method for preparing a composite positive electrode active material may include the steps of: providing a lithium transition metal oxide; providing a second composite; and mechanically grinding the lithium transition metal oxide and the second composite, wherein the second composite includes at least one first metal oxide represented by the formula M a O b (where 0 < a ≤ 3, 0 < b < 4, a is 1, 2, or 3, and b is not an integer) and a first carbonaceous material, wherein the first metal oxide is disposed in a matrix of the first carbonaceous material, and M is at least one metal selected from Groups 2 to 16 of the periodic table.

[0191] Provide a lithium transition metal oxide. The lithium transition metal oxide may include, for example, a compound represented by a formula selected from the above formulas 1 to 5.

[0192] Provide a second composite. The step of providing the second composite may include, for example, supplying a reaction gas including a carbon source gas to a structure including a second metal oxide and heat-treating the structure to provide the second composite. The step of providing the second composite may include, for example, supplying a reaction gas including a carbon source gas to at least one second metal oxide represented by M a O c (where 0 < a ≤ 3, 0 < c ≤ 4, and if a is 1, 2, or 3, then b is an integer), and heat-treating the second metal oxide to prepare the second composite, wherein M is at least one metal selected from Groups 2 to 16 of the periodic table.

[0193] The carbon source gas may be a gas including a compound represented by the following formula 7, or may be at least one mixed gas selected from a compound represented by the following formula 7, a compound represented by the following formula 8, and an oxygen-containing gas represented by the following formula 9.

[0194] Formula 7

[0195] C n H (2n+2-a) [OH] a

[0196] In Formula 7, n can be from 1 to 20, and a can be 0 or 1.

[0197] Formula 8

[0198] C n H 2n

[0199] In Formula 8, n can be from 2 to 6.

[0200] Formula 9

[0201] C x H y O z

[0202] In Formula 9, x can be 0 or an integer from 1 to 20, y can be 0 or an integer from 1 to 20, and z can be 1 or 2.

[0203] The compound represented by Formula 7 and the compound represented by Formula 8 can include at least one selected from methane, ethylene, propylene, methanol, ethanol, and propanol. The oxygen-containing gas represented by Formula 9 can include, for example, carbon dioxide (CO2), carbon monoxide (CO), water vapor (H2O), or a mixture thereof.

[0204] After supplying a reaction gas including a carbon source gas to a second metal oxide represented by M a O c (where 0 < a ≤ 3, 0 < c ≤ 4, and if a is 1, 2, or 3, then b is an integer), cooling using at least one inert gas selected from nitrogen, helium, and argon can be further performed. Cooling refers to an operation of adjusting the temperature to room temperature (20 °C to 25 °C). The cooling gas can include at least one inert gas selected from nitrogen, helium, and argon.

[0205] In the method for preparing the second composite, the process of growing the first carbonaceous material (e.g., graphene) by gas-phase reaction can be carried out under various conditions.

[0206] According to the first condition, for example, first, methane is supplied to a reactor in which M a O cA reactor of a second metal oxide represented by (where 0 < a ≤ 3, 0 < c ≤ 4, and if a is 1, 2, or 3, then b is an integer), and the temperature is raised to a heat treatment temperature T. The time taken to raise the temperature to the heat treatment temperature T can be about 10 minutes to about 4 hours, and the heat treatment temperature T can be in the range of about 700 °C to about 1100 °C. Heat treatment can be carried out for a certain reaction time at the heat treatment temperature T. The reaction time can be, for example, about 4 hours to about 8 hours. The heat treatment product can be cooled to room temperature to prepare the second composite. The time taken during the process of cooling from the heat treatment temperature T to room temperature can be, for example, about 1 hour to about 5 hours.

[0207] According to the second condition, for example, first, hydrogen is supplied to a reactor in which a second metal oxide represented by M a O c (where 0 < a ≤ 3, 0 < c ≤ 4, and if a is 1, 2, or 3, then b is an integer) is provided, and the temperature is raised to a heat treatment temperature T. The time taken to raise the temperature to the heat treatment temperature T can be about 10 minutes to about 4 hours, and the heat treatment temperature T can be in the range of about 700 °C to about 1100 °C. After heat treatment is carried out for a certain reaction time at the heat treatment temperature T, methane gas can be supplied, and heat treatment can be carried out for the remaining reaction time. The reaction time can be, for example, about 4 hours to about 8 hours. The heat treatment product can be cooled to room temperature to prepare the second composite. Nitrogen can be supplied during the cooling process. The time taken during the process of cooling from the heat treatment temperature T to room temperature can be, for example, about 1 hour to about 5 hours.

[0208] According to the third condition, for example, first, hydrogen is supplied to a reactor in which a second metal oxide represented by M a O c (where 0 < a ≤ 3, 0 < c ≤ 4, and if a is 1, 2, or 3, then b is an integer) is provided, and the temperature is raised to a heat treatment temperature T. The time taken to raise the temperature to the heat treatment temperature T can be about 10 minutes to about 4 hours, and the heat treatment temperature T can be in the range of about 700 °C to about 1100 °C. After heat treatment is carried out for a certain reaction time at the heat treatment temperature T, a mixed gas of methane and hydrogen can be supplied, and heat treatment can be carried out for the remaining reaction time. The reaction time can be, for example, about 4 hours to about 8 hours. The heat treatment product can be cooled to room temperature to prepare the second composite. Nitrogen can be supplied during the cooling process. The time taken during the process of cooling from the heat treatment temperature T to room temperature can be, for example, about 1 hour to about 5 hours.

[0209] In the process of preparing the second composite, if the carbon source gas includes water vapor, a second composite having very excellent electrical conductivity can be obtained. The content of water vapor in the gas mixture is not limited, and can be, for example, in the range of about 0.01 volume % to about 10 volume % relative to about 100 volume % of the total carbon source gas. The carbon source gas can include, for example, methane, a mixed gas including methane and an inert gas, or a mixed gas including methane and an oxygen-containing gas.

[0210] The carbon source gas may include, for example, methane, a mixed gas of methane and carbon dioxide, or a mixed gas of methane, carbon dioxide and water vapor. The molar ratio of methane to carbon dioxide in the mixed gas of methane and carbon dioxide is about 1:0.20 to 1:0.50, about 1:0.25 to 1:0.45, or about 1:0.30 to 1:0.40. The molar ratio of methane to carbon dioxide to water vapor in the mixed gas of methane, carbon dioxide and water vapor may be in the range of about 1:0.20 to about 0.50:0.01 to 1.45, about 1:0.25 to about 0.45:0.10 to 1.35, or about 1:0.30 to about 0.40:0.50 to 1.0.

[0211] The carbon source gas may include, for example, carbon monoxide or carbon dioxide. The carbon source gas may include, for example, a mixed gas of methane and nitrogen. The molar ratio of methane to nitrogen in the mixed gas of methane and nitrogen may be in the range of about 1:0.20 to about 1:0.50, about 1:0.25 to about 1:0.45, or about 1:0.30 to about 1:0.40. The carbon source gas may not include an inert gas such as nitrogen.

[0212] The heat treatment pressure can be selected considering the heat treatment temperature, the composition of the gas mixture and the required carbon coating amount. The heat treatment pressure can be controlled by adjusting the inflow of the gas mixture and the outflow of the gas mixture. The heat treatment pressure can be, for example, 0.5atm or more, 1atm or more, 2atm or more, 3atm or more, 4atm or more, or 5atm or more. The heat treatment pressure can be, for example, in the range of about 0.5atm to about 10atm, about 1atm to about 10atm, about 2atm to about 10atm, about 3atm to about 10atm, about 4atm to about 10atm, or about 5atm to about 10atm.

[0213] The heat treatment time is not particularly limited and can be appropriately adjusted according to the heat treatment temperature, heat treatment pressure, composition of the gas mixture, and the desired amount of carbon coating. For example, the reaction time at the heat treatment temperature can be, for example, about 10 minutes to about 100 hours, about 30 minutes to about 90 hours, or about 50 minutes to about 40 hours. For example, as the heat treatment time increases, the amount of deposited carbon (e.g., the amount of graphene (carbon)) can increase, and thus the electrical properties of the second composite can be improved. However, this trend may not necessarily be proportional to the time. For example, after a certain period of time, carbon deposition (e.g., graphene deposition) may no longer occur, or the deposition rate may decrease.

[0214] Through the above gas-phase reaction of the carbon source gas, even at a relatively low temperature, the first carbonaceous material (e.g., graphene) can be uniformly coated on at least one of the second metal oxides represented by M a O c (where 0 < a ≤ 3, 0 < c ≤ 4, and if a is 1, 2, or 3, then c is an integer) and the first metal oxides represented by M a O b (0 < a ≤ 3, 0 < b < 4, a is 1, 2, or 3, and b is not an integer) which are the reduction products thereof, thereby obtaining a second composite.

[0215] The second composite may include, for example, a matrix (e.g., a graphene matrix) of the first carbonaceous material having at least one structure selected from a spherical structure, a helical structure in which a plurality of spherical structures are connected, a cluster structure in which a plurality of spherical structures are aggregated, and a sponge structure, and at least one selected from the first metal oxides represented by M a O b (0 < a ≤ 3, 0 < b < 4, a is 1, 2, or 3, and b is not an integer) and the second metal oxides represented by M a O c (0 < a ≤ 3, 0 < c ≤ 4, and if a is 1, 2, or 3, then c is an integer) provided in the graphene matrix.

[0216] Next, the lithium transition metal oxide and the second composite can be mechanically ground.

[0217] In the mechanical grinding, the grinding method is not particularly limited, and any method can be used as long as it is a method of bringing the lithium transition metal oxide into contact with the second composite using a machine and is available in the art.

[0218] During grinding, for example, a Novilta mixer or the like can be used. The rotation speed of the mixer during grinding can be, for example, in the range of about 1,000 rpm to about 5,000 rpm. The grinding time can be, for example, about 5 minutes to about 100 minutes, about 5 minutes to about 60 minutes, or about 5 minutes to about 30 minutes.

[0219] The average particle diameter (D50) of the second composite used in the step of mechanically grinding the first lithium transition metal oxide and the second composite can be, for example, in the range of about 50 nm to about 200 nm, about 100 nm to about 300 nm, or about 200 nm to about 500 nm.

[0220] Hereinafter, the disclosure will be described in more detail by the following examples and comparative examples. However, the following examples and comparative examples are presented only for illustrative purposes of the disclosure, and the scope of the disclosure is not limited thereto.

[0221] (Preparation of Composite)

[0222] Preparation Example 1: Al2O3@Gr composite

[0223] After placing Al2O3 particles (average particle diameter: about 20 nm) in a reactor, the internal temperature of the reactor was raised to 1000 °C under the condition that CH4 was supplied to the reactor at a rate of about 300 sccm and a pressure of 1 atm for about 30 minutes.

[0224] Subsequently, heat treatment was carried out while maintaining the temperature at 1000 °C for 7 hours. Then, the internal temperature of the reactor was adjusted to room temperature (20 °C to 25 °C) to obtain a composite in which Al2O3 particles and Al2O as its reduction product z (where 0 < z < 3) are embedded in graphene.

[0225] The content of alumina included in the composite is 60 wt%.

[0226] (Preparation of Composite Positive Electrode Active Material)

[0227] Example 1: 0.05wt% Al2O3@Gr composite (alumina 0.03wt%) coated NCA94

[0228] LiNi with an average particle diameter of 14 μm 0.94 Co 0.02 Al 0.02 O2 (hereinafter referred to as NCA94) and the composite prepared in Preparation Example 1 were ground for about 5 minutes to about 30 minutes at a rotation speed of about 1,000 to about 2,000 rpm using a Nobilta mixer (manufactured by Hosokawa Micron Corporation, Japan) to prepare a composite positive electrode active material. NCA94 and the composite were mixed at a ratio of 99.95:0.05 to prepare a composite positive electrode active material.

[0229] like Figure 2 As shown in , it is confirmed that carbon nanotubes are provided on the surface of the composite positive electrode active material. The carbon nanotubes include a carbon nanotube primary structure and a carbon nanotube secondary structure formed by aggregating a plurality of carbon nanotube units.

[0230] The carbon nanotube primary structure includes one carbon nanotube unit. The carbon nanotube unit has a length of 200 nm to about 1,000 nm, and the carbon nanotube has a diameter of about 10 nm.

[0231] The carbon nanotube secondary structure is formed by aggregating a plurality of carbon nanotube units. The carbon nanotube secondary structure has a length of 3,000 nm or more and a diameter of about 40 nm.

[0232] Example 2: 0.1wt% Al2O3@Gr composite coated NCA94

[0233] A composite positive electrode active material was prepared in the same manner as in Example 1, except that the mixing ratio of NCA94 to the composite was changed to 99.9:0.1.

[0234] Example 3: 0.4wt% Al2O3@Gr composite coated NCA94

[0235] A composite positive electrode active material was prepared in the same manner as in Example 1, except that the mixing ratio of NCA94 to the composite was changed to 99.6:0.4.

[0236] Comparative Example 1: Bare NCA94

[0237] NCA94 with an average particle size of 14 μm was used as the composite positive electrode active material.

[0238] Comparative Example 2: 0.25wt% LZO coated NCA94

[0239] As the positive electrode active material, LiNi coated with 0.25 wt% LZO was prepared. 0.94 Co 0.02 Al 0.02 O2 (NCA94). A positive electrode active material coated with LZO was prepared according to the method disclosed in Korean Patent Publication No. 10-2016-0064942.

[0240] (Manufacturing of all-solid-state secondary batteries)

[0241] Example 4

[0242] (Preparation of positive electrode)

[0243] As a positive electrode active material, the composite positive electrode active material prepared in Example 1 was prepared. As a solid electrolyte, a mixture of crystalline Li6PS5Cl with an average particle size of 3 μm and crystalline Li6PS5Cl with an average particle size of 1 μm, both as argyrodite-type crystals, was prepared in a weight ratio of 3:1. As a conductive material, carbon nanofibers (CNF) were prepared. A mixture of a positive electrode active material, a solid electrolyte and a conductive material in a weight ratio of 60:35:5 was prepared. After adding a binder solution and mixing so that the binder was included at 2 wt% relative to the total weight of the mixture, the mixture was molded into a sheet form and dried to prepare a positive electrode sheet. The prepared positive electrode sheet was pressed onto one surface of a positive electrode current collector made of a carbon-coated aluminum foil having a thickness of 18 μm to prepare a positive electrode layer.

[0244] (Preparation of Solid Electrolyte Layer)

[0245] 1 part by weight of SBR binder relative to 100 parts by weight of solid electrolyte is added to a crystalline Li6PS5Cl solid electrolyte having an average particle size of 3 μm to prepare a mixture. Xylene and diethylbenzene are added to the prepared mixture and stirred to prepare a slurry. The prepared slurry is applied to a nonwoven fabric using a blade coater and dried in air at a temperature of 40°C to obtain a stack. The resulting stack is vacuum dried at a temperature of 40°C for 12 hours. A solid electrolyte layer is prepared by such a process.

[0246] (Manufacturing of all-solid-state secondary batteries)

[0247] A solid electrolyte layer is disposed on one surface of a positive electrode layer on the bottom of a container, a Li-In alloy foil as a negative electrode active material layer is disposed on the solid electrolyte layer, and a SUS current collector is disposed on the Li-In alloy foil to prepare a stack. The lid of the container is rotated to press the prepared stack, thereby manufacturing a torque cell. The solid electrolyte layer is sintered by such a pressing process, thereby improving battery characteristics.

[0248] Example 5 and Example 6

[0249] A torque cell was manufactured in the same manner as in Example 4, except that the composite positive electrode active materials prepared in Examples 2 and 3 were used respectively instead of the composite positive electrode active material prepared in Example 1.

[0250] Comparative Example 3 and Comparative Example 4

[0251] A torque cell was manufactured in the same manner as in Example 4, except that the composite positive electrode active materials prepared in Comparative Examples 1 and 2 were used instead of the composite positive electrode active material prepared in Example 1, respectively.

[0252] Evaluation Example 1: X-ray Photoelectron Spectroscopy (XPS) Spectral Evaluation

[0253] In the process of preparing the composite prepared in Preparation Example 1, the XPS spectrum was measured over time using Qunatum 2000 (manufactured by Physical Electronics Co., Ltd.). Before heating, the XPS spectra of the C1s orbital and the Al 2p orbital of the sample were measured after 1 minute, 5 minutes, 30 minutes, 1 hour, and 4 hours, respectively. At the time of initial heating, only the peak of the Al 2p orbital appeared, and the peak of the C1s orbital did not appear. After 30 minutes, the peak of the C1s orbital appeared clearly, and the size of the peak of the Al2p orbital was significantly reduced.

[0254] After 30 minutes, a peak of the C1s orbital clearly appears at around 284.5 eV due to the CC bond and C═C bond generated by the growth of graphene.

[0255] As the reaction time elapses, the oxidation number of aluminum decreases, and thus the peak position of the Al 2p orbital shifts toward lower binding energy (eV).

[0256] Therefore, it was confirmed that as the reaction proceeded, graphene grew on the Al2O3 particles and Al2O3 was generated as a reduction product of Al2O3. x (Among them, 0 <x<3)。

[0257] Through the XPS analysis results, the average contents of carbon and aluminum were measured in 10 regions of the composite sample prepared in Preparation Example 1. For the measurement results, the deviation of the aluminum content in each region was calculated. The deviation of the aluminum content was expressed as a percentage of the average value, and the percentage was called uniformity. The percentage of the average value of the deviation of the aluminum content (i.e., the uniformity of the aluminum content) was 1%. Therefore, it was confirmed that aluminum oxide was uniformly distributed in the composite prepared in Preparation Example 1.

[0258] Evaluation Example 2: SEM, HR-TEM and SEM-EDS analysis

[0259] The composite prepared in Preparation Example 1, the composite positive electrode active material prepared in Example 1, and the composite positive electrode active material prepared in Comparative Example 1 were analyzed by scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HR-TEM), and energy dispersive X-ray spectroscopy (EDS).

[0260] For EM-EDS analysis, FEI Titan 80-300 manufactured by Philips was used.

[0261] The composite prepared in Preparation Example 1 has Al2O3 particles and Al2O3 as a reduction product thereof. zStructure in which particles (where 0 < z < 3) are embedded in graphene. It is confirmed that the graphene layer is disposed at the periphery of at least one of the particles selected from Al2O3 particles and Al2O z (0 < z < 3) particles. At least one of the particles selected from Al2O3 particles and Al2O z particles (where 0 < z < 3) are uniformly distributed. At least one of the particles selected from Al2O3 particles and Al2O z particles (where 0 < z < 3) has a particle size of about 20 nm. The composite prepared in Preparation Example 1 has a particle size of about 50 nm to about 200 nm. In the composite positive electrode active material prepared in Example 1, it is confirmed that a shell formed of a composite including graphene is disposed on the NCA94 core.

[0262] In the SEM-EDS mapping analysis of the composite positive electrode active materials prepared in Comparative Example 1 and Example 1, it is confirmed that the concentration of aluminum (Al) distributed on the surface of the composite positive electrode active material of Example 1 is increased compared to the surface of the composite positive electrode active material of Comparative Example 1.

[0263] As Figure 9a and Figure 9b shown, it is confirmed that the concentration of aluminum (Al) distributed on the surface of the composite positive electrode active material of Example 1, which is a secondary particle aggregated with a plurality of primary particles, is increased.

[0264] In the composite positive electrode active material of Example 1, it is confirmed that the composite prepared in Preparation Example 1 is coated on the NCA94 core to form a shell.

[0265] Evaluation Example 3: XPS Spectrum Evaluation (Graphene-NCA94 Chemical Bond)

[0266] For the composite prepared in Preparation Example 1, the NCA94 of Comparative Example 1, and the composite positive electrode active material prepared in Example 1, the XPS spectrum of the O1s orbital was measured using Quantum 2000 (manufactured by Physical Electronics Co., Ltd.). The results are shown in Fig.10 shown.

[0267] As Fig.10 shown, for the composite positive electrode active material of Example 1, a peak due to the C-O-Ni bond is observed near 530.2 eV. Such a peak is determined to be due to the bond formed between the NiO phase present on the surface of NCA94 and the carbon of graphene. Therefore, it is confirmed that the graphene included in the shell formed on the core forms a covalent bond with Ni, which is a transition metal included in the core.

[0268] Evaluation Example 4: Raman spectroscopy evaluation (graphene-NCA94 chemical bond)

[0269] Raman spectra were measured for the composite prepared in Preparation Example 1 and the composite positive electrode active material prepared in Example 1. The results are shown in Fig.11 Shown in.

[0270] like Fig.11 As shown in FIG. , the composite prepared in Preparation Example 1 has a large surface area at 1,338.7 cm due to graphene. -1 There is a D band peak at 1575.0 cm -1 It shows a G band peak.

[0271] On the other hand, in the composite positive electrode active material of Example 1, due to the inclusion of the graphene shell, the D band peak is oriented to 1,351.3 cm -1 Move about 12cm -1 , G band peak to 1,593.6cm -1 Move about 18cm -1 .

[0272] It was determined that the shift of the D band peak was due to the strain of graphene bonded to the core to form a shell by milling.

[0273] If the core and graphene form a composite via CO-Ni bonds, the shift of the G band peak is determined to be due to the charge transfer between the core and graphene.

[0274] Therefore, it was confirmed that graphene included in the shell formed on the core formed a covalent bond with Ni which was a transition metal included in the core.

[0275] Evaluation Example 5: Evaluation of residual lithium content on the surface

[0276] The surface residual lithium content was measured for the composite positive electrode active materials prepared in Examples 1 to 3 and Comparative Example 1. Some of the results are shown in Table 1 below.

[0277] The surface residual lithium content was evaluated by measuring the Li content in Li2CO3 and LiOH remaining on the surface of the composite positive electrode active material by a wet method (or titration method).

[0278] For a specific measurement method, reference may be made to the method disclosed in paragraph

[0054] of Japanese Patent Laid-Open No. 2016-081903, for example.

[0279] [Table 1]

[0280] Residual lithium content [ppm] Comparative Example 1 4,109 Example 1 4,083 Example 2 3,541 Example 3 2,870

[0281] As shown in Table 1, in the composite positive electrode active materials of Examples 1 to 3, compared with the composite positive electrode active material of Comparative Example 1, the surface residual lithium content was reduced.

[0282] It was determined that this was because residual lithium on the surface of the lithium transition metal oxide (core) reacted with the composite to form a shell on the core.

[0283] Therefore, as compared with the lithium battery including the composite positive electrode active material of Comparative Example 1, in the lithium battery including the composite positive electrode active material of each of Examples 1 to 3, the side reaction with the solid electrolyte is suppressed during charge / discharge, thereby improving the life characteristics.

[0284] Evaluation Example 6: Evaluation of charge / discharge characteristics at high temperature (45° C.)

[0285] The all-solid-state secondary batteries manufactured in Examples 4 to 6 and Comparative Examples 3 to 4 were charged at a constant current rate of 0.1C at a temperature of 45°C until the voltage reached 3.63V (vs. Li-In), and then, in constant voltage mode, while maintaining 3.63V, the charging was cut off at a current rate of 0.05C. Subsequently, during discharge, the all-solid-state secondary battery was discharged at a constant current rate of 0.1C until the voltage reached 1.88V (vs. Li-In) (first cycle). Such a cycle was repeated under the same conditions until the 50th cycle.

[0286] After each charge / discharge cycle, the all-solid-state secondary battery was left to stand for 10 minutes. The results of the charge / discharge test at high temperature are shown in Table 2 below. The capacity retention rate is defined by Equation 1 below.

[0287] Equation 1

[0288] Capacity retention rate (%) = [discharge capacity at the 50th cycle / discharge capacity at the 1st cycle] × 100

[0289] Evaluation Example 7: Interface Resistance Evaluation

[0290] The interface resistances of the all-solid-state secondary batteries manufactured in Examples 4 to 6 and Comparative Examples 3 and 4 were measured before and after evaluation of charge / discharge characteristics, respectively, and the results are shown in Table 2 below.

[0291] The interface resistance R was obtained by measuring the impedance of the all-solid-state secondary battery by a double probe method using an impedance analyzer (Solartron 1400A / 1455A impedance analyzer). ct The frequency range was 0.1 Hz to 1 MHz, and the amplitude voltage was 10 mV. The measurement was performed at a temperature of 25° C. in an air atmosphere.

[0292] [Table 2]

[0293]

[0294] As shown in Table 2, in the all-solid-state secondary batteries of Examples 4 to 6, the interface resistance before the charge / discharge characteristic evaluation increased compared to the all-solid-state secondary batteries of Comparative Examples 3 and 4, but the interface resistance decreased after the charge / discharge characteristic evaluation.

[0295] In addition, in the all-solid-state secondary batteries of Examples 4 to 6, lifespan characteristics were improved compared to the all-solid-state secondary batteries of Comparative Examples 3 and 4.

[0296] As compared with the composite positive electrode active material without coating of Comparative Example 3 and the composite positive electrode active material including a metal oxide coating of Comparative Example 4, in the composite positive electrode active materials of Examples 4 to 6 including a carbon coating, the initial interface resistance before evaluating the charge / discharge characteristics increased, but during the charge / discharge process, the side reaction between the positive electrode active material and the solid electrolyte was suppressed, thereby suppressing the increase in interface resistance, and thus determining that the life characteristics were significantly improved.

[0297] Industrial Applicability

[0298] According to one aspect, using a novel positive electrode, a side reaction between a lithium transition metal oxide and a solid electrolyte can be suppressed, thereby providing an all-solid-state secondary battery with improved cycle characteristics.

Claims

1. A positive electrode for an all-solid-state secondary battery, the positive electrode comprising: positive electrode current collector; as well as A positive electrode active material layer is disposed on the positive electrode current collector, The positive electrode active material layer comprises a composite positive electrode active material and a sulfide solid electrolyte. The composite positive electrode active material comprises: a core comprising a lithium transition metal oxide; and a shell disposed on a surface of the core, The shell includes at least one first metal oxide and a first carbon-based material, The first metal oxide is disposed in a matrix of the first carbon-based material, The at least one first metal oxide is represented by the formula M a O b where 0 < a ≤ 3, 0 < b < 4, and if a is 1, 2, or 3, then b is not an integer, and M is at least one metal selected from Groups 2 to 16 of the Periodic Table of the Elements. The lithium transition metal oxide includes nickel, and The nickel content is 80 mol% or more relative to the total moles of the transition metal.

2. The positive electrode according to claim 1, wherein The at least one first metal oxide includes a first metal, and the first metal includes at least one selected from Al, Nb, Mg, Sc, Ti, Zr, V, W, Mn, Fe, Co, Pd, Cu, Ag, Zn, Sb, Si and Se.

3. The positive electrode according to claim 1, wherein The first metal oxide includes at least one selected from the following: Al2O z , where 0 < z < 3; NbO x , where 0 < x < 2.5; MgO x , where 0 < x < 1; Sc2O z , where 0 < z < 3; TiO y , where 0 < y < 2; ZrO y , where 0 < y < 2; V2O z , where 0 < z < 3; WO y , where 0 < y < 2; MnO y , where 0 < y < 2; Fe2O z , where 0 < z < 3; Co3O w , where 0 < w < 4; PdO x , where 0 < x < 1; CuO x , where 0 < x < 1; AgO x , where 0 < x < 1; ZnO x , where 0 < x < 1; Sb2O z , where 0 < z < 3; SiO z , where 0 < z < 2; and SeO y , where 0 < y < 2.

4. The positive electrode according to claim 1, wherein The shell further includes a second metal oxide, The second metal oxide is represented by the formula M a O c where 0 < a ≤ 3, 0 < c ≤ 4, and if a is 1, 2, or 3, then c is an integer. The second metal oxide comprises the same metal as the first metal oxide, The value of the ratio c / a of the second metal oxide to a is greater than the value of the ratio b / a of the first metal oxide to a, and The second metal oxide is disposed in the matrix of the first carbon-based material.

5. The positive electrode according to claim 4, wherein The second metal oxide is selected from the group consisting of Al2O3, NbO, NbO2, Nb2O5, MgO, Sc2O3, TiO2, ZrO2, V2O3, WO2, MnO2, Fe2O3, Co3O4, PdO, CuO, AgO, ZnO, Sb2O3, SiO2 and SeO2, and The first metal oxide is a reduction product of the second metal oxide.

6. The positive electrode according to claim 1, wherein The first carbon-based material included in the shell is chemically bonded to the transition metal of the lithium transition metal oxide included in the core through a chemical bond, The carbon atoms (C) of the first carbon-based material included in the shell are chemically bonded to the transition metal (Me) of the lithium transition metal oxide through a CO-Me bond using oxygen atoms, and The at least one first metal oxide is chemically combined with the first carbon-based material through a chemical bond.

7. The positive electrode according to claim 1, wherein The shell further comprises a second carbon-based material, a third metal oxide, or a combination thereof, The second carbon-based material is a fibrous carbon-based material, The third metal oxide is a lithium metal oxide, and The lithium metal oxide includes lithium aluminum oxide, lithium titanium oxide, lithium zirconium oxide, lithium zirconium phosphate or a combination thereof.

8. The positive electrode according to claim 1, wherein The shell has a thickness of 10 nm to 2 μm, has a single-layer structure or a multi-layer structure, and is a dry coating, and The content of the shell is 5 wt % or less relative to the total weight of the composite positive electrode active material.

9. The positive electrode according to claim 1, wherein The lithium transition metal oxide is represented by a formula selected from the following Formula 1 to Formula 5: Formula 1 Li a Ni x Co y M z O 2-b A b Wherein, in Formula 1, 1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0.8 ≤ x < 1, 0 ≤ y ≤ 0.3, 0 < z ≤ 0.3, x + y + z = 1, M is manganese (Mn), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B) or a combination thereof, and A is F, S, Cl, Br or a combination thereof. Formula 2 LiNi x Co y Mr z O2 Formula 3 LiNi x Co y Al z O2 Wherein, in Formulas 2 and 3, 0.8 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.2, 0 < z ≤ 0.2, and x + y + z = 1. Formula 4 LiNi x Co y Mr z Al w O2 Wherein, in Formula 4, 0.8 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.2, 0 < z ≤ 0.2, 0 < w ≤ 0.2, and x + y + z + w = 1, and Formula 5 Li a Ni x Mr y M' z O 2-b A b Wherein, in Formula 5, 1.0 ≤ a ≤ 1.2, 0 ≤ b ≤ 0.2, 0.8 ≤ x < 1, 0 < y ≤ 0.2, 0 ≤ z ≤ 0.2, x + y + z = 1, M' is niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B) or a combination thereof, and A is F, S, Cl, Br or a combination thereof.

10. The positive electrode according to claim 1, wherein The composite positive electrode active material includes a first composite positive electrode active material and a second composite positive electrode active material. The first composite positive electrode active material is a large-diameter composite positive electrode active material having a particle diameter larger than that of the second composite positive electrode active material, and The second composite positive electrode active material is a small-diameter composite positive electrode active material having a particle diameter smaller than that of the first composite positive electrode active material.

11. The positive electrode according to claim 10, wherein The first composite positive electrode active material includes secondary particles aggregated with a plurality of primary particles, or includes primary particles having a particle diameter of 1 μm or more, and The second composite positive electrode active material includes secondary particles aggregated with a plurality of primary particles, or includes primary particles having a particle diameter of 1 μm or more.

12. The positive electrode according to claim 10, wherein The first composite positive electrode active material and the second composite positive electrode active material have a bimodal particle size distribution in the particle size distribution, and The particle diameter ratio of the first composite positive electrode active material to the second composite positive electrode active material is in the range of 3:1 to 40:

1.

13. The positive electrode according to claim 10, wherein The first composite positive electrode active material has a particle diameter greater than 8 μm and less than or equal to 30 μm, and the second composite positive electrode active material has a particle diameter greater than or equal to 1 μm and less than 8 μm, and The weight ratio of the first composite positive electrode active material to the second composite positive electrode active material is in the range of 90:10 to 60:

40.

14. The positive electrode according to claim 1, wherein The sulfide solid electrolyte includes a crystalline sulfide solid electrolyte, an amorphous sulfide solid electrolyte, a glassy sulfide solid electrolyte, a glass-ceramic sulfide solid electrolyte or a combination thereof, and includes at least one selected from the following: Li2S-P2S5; Li2S-P2S5-LiX, wherein X is a halogen element; Li2S-P2S5-Li2O; Li2S-P2S5-Li2O-LiI; Li2S-SiS2; Li2S-SiS2-LiI; Li2S-SiS2-LiBr; Li2S-SiS2-LiCl; Li2S-SiS2-B2S3-LiI; Li2S-SiS2-P2S5-LiI; Li2S-B2S3; Li2S-P2S5-Z m S n , wherein m and n are each positive numbers, and Z is one selected from Ge, Zn and Ga; Li2S-GeS2; Li2S-SiS2-Li3PO4; Li2S-SiS2-Li p MO q , wherein p and q are each positive numbers, and M is one selected from P, Si, Ge, B, Al, Ga and In; Li 7-x PS 6- x Cl x , where 0≤x≤2; Li 7-x PS 6-x Br x , where 0≤x≤2; and Li 7-x PS 6-x I x , where 0≤x≤2.

15. The positive electrode according to claim 1, wherein The sulfide-based solid electrolyte is a thiogermanate-type solid electrolyte including at least one selected from Li6PS5Cl, Li6PS5Br, and Li6PS5I, and The thiogermanate-type solid electrolyte has a density of 1.5 g / cc to 2.0 g / cc.

16. The positive electrode according to claim 1, wherein The sulfide-based solid electrolyte has a particle form and includes a first sulfide-based solid electrolyte and a second sulfide-based solid electrolyte, The first sulfide-based solid electrolyte and the second sulfide-based solid electrolyte have different particle sizes from each other.

17. The positive electrode according to claim 16, wherein the first sulfide-based solid electrolyte is a large-diameter sulfide-based solid electrolyte having a particle size larger than that of the second sulfide-based solid electrolyte, the second sulfide-based solid electrolyte is a small-diameter sulfide-based solid electrolyte having a particle size smaller than that of the first sulfide-based solid electrolyte, In the particle size distribution of the sulfide-based solid electrolyte, the sulfide-based solid electrolyte has a bimodal particle size distribution having a first peak corresponding to the first sulfide-based solid electrolyte and a second peak corresponding to the second sulfide-based solid electrolyte, and A particle size ratio of the first sulfide-based solid electrolyte to the second sulfide-based solid electrolyte is in a range of 2:1 to 10:

1.

18. The positive electrode according to claim 16, wherein The first sulfide-based solid electrolyte has a particle size of 1 μm to 10 μm, and the second sulfide-based solid electrolyte has a particle size of 0.1 μm to 2 μm, and A weight ratio of the first sulfide-based solid electrolyte to the second sulfide-based solid electrolyte is in a range of 50:50 to 90:

10.

19. The positive electrode according to claim 1, wherein The positive electrode active material layer also includes a conductive material and a binder. The conductive material comprises at least one selected from a fibrous conductive material and a granular conductive material, and The binder includes a fluorine-based binder.

20. An all-solid-state secondary battery, comprising: The positive electrode according to any one of claims 1 to 19; Negative electrode; as well as A solid electrolyte layer is disposed between the positive electrode and the negative electrode.

21. The all-solid-state secondary battery according to claim 20, wherein: The electrolyte layer includes an electrolyte, Wherein, the electrolyte is a solid electrolyte, a gel electrolyte or a combination thereof, The solid electrolyte includes a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte or a combination thereof. Wherein, the gel electrolyte comprises a polymer gel electrolyte.

22. The all-solid-state secondary battery according to claim 20, wherein: The positive electrode comprises a positive electrode current collector, The negative electrode comprises a negative electrode current collector, At least one of the positive electrode current collector and the negative electrode current collector includes a base film and a metal layer provided on one surface or both surfaces of the base film, The base film comprises a polymer, The polymer includes polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof, and The metal layer includes indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li) or alloys thereof.

Citation Information

Patent Citations

  • Positive electrode active material for lithium ion secondary battery, method of producing the same, and lithium ion secondary battery

    JP2016081903A

Cited By

  • Conductive network coating modified high-nickel ternary positive electrode material and preparation method thereof

    CN121172122A

  • A conductive network coating modified high-nickel ternary cathode material and its preparation method

    CN121172122B